Zirconia composite powder, dental restoration and preparation method thereof
By adding dispersant, antistatic agent and binder to the zirconia powder to form a composite powder, the mixing and forming unevenness of zirconia powder in dental restorations is solved, and the color uniformity and strength of dental restorations are improved.
Patent Information
- Application Number
- CN202411996388.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-08
AI Technical Summary
There is unevenness in the existing zirconia powders during mixing and dry press forming, resulting in poor color uniformity and low intensity of dental restorations.
A zirconia composite powder is used, and by adding dispersant, antistatic agent and binder to the stabilized zirconia powder, the slurry is formed and the powder is dried to improve the flowability and mixing uniformity of the powder.
It improves the color uniformity and strength of the dental restoration after porcelain formation, ensuring the functional and aesthetic performance of the dental restoration.
Smart Images

Figure CN119775005A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of zirconium oxide dental restorations, and in particular to a zirconium oxide composite powder, a dental restoration and a preparation method thereof. Background Art
[0002] Zirconia has excellent chemical inertness and biocompatibility, making it very suitable for use in the medical field. Its high hardness and good biocompatibility make it an ideal material for dental restorations. Its good strength and toughness enable zirconia to withstand large bite forces without breaking or disintegrating. At the same time, its natural color and translucency can simulate the appearance of natural teeth, and it has both aesthetic functions while satisfying its functionality. In particular, stabilized zirconia, such as yttrium-stabilized zirconia, has even better performance. Therefore, zirconia materials have become the first choice for dental restorations, all-ceramic crowns, dental bridges and other restoration materials.
[0003] In order to approach the color and gloss of natural teeth, zirconium oxide powder is usually dry-mixed with colored powder. However, when zirconium oxide powders of different components are mixed, uneven mixing will occur, which will lead to uneven mixing with colored powders in the subsequent mixing, and poor color uniformity after porcelain formation, which directly affects the appearance. In addition, in the dry pressing process, due to the uneven distribution of zirconium oxide powder, the powder cannot fully fill the mold, resulting in uneven pressing, reducing the uniformity of the density of the green body, and local defects may appear inside the green body, thus affecting the subsequent firing performance and the strength of the porcelain after formation.
[0004] Therefore, how to improve the fluidity of zirconium oxide powders with different colors used to make dental restorations, so as to improve the mixing uniformity between zirconium oxide powders without colorants and nearly pure white in color and zirconium oxide powders with colorants, so as to obtain dental restorations with better color uniformity and higher strength after porcelain formation, is a problem that needs to be urgently solved in the field. Summary of the invention
[0005] The object of the present invention is to provide a zirconium oxide composite powder, a dental restoration and a preparation method thereof, which can improve the mixing uniformity between a zirconium oxide composite powder without a colorant and having a color of nearly pure white and a zirconium oxide composite powder containing a colorant and having a color, thereby improving the fluidity of zirconium oxide powders with different colors used to make dental restorations, thereby obtaining a dental restoration with better color uniformity and higher strength after porcelain formation.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] A zirconium oxide composite powder, the components of which include: stabilized zirconium oxide powder and an additive;
[0008] Wherein, the auxiliary agent includes:
[0009] The dispersant is preferably at least one of propylene glycol methyl ether, sodium polymethacrylate, polyacrylamide, sodium oleate, polyethylene ether, sodium hexametaphosphate, and sodium tripolyphosphate;
[0010] The antistatic agent is preferably at least one of glycerol fatty acid ester, lauryl alcohol, dodecanol, n-octanol, glycerol, polyethylene glycol, diethylene glycol methyl ether, and octadecylamine polyoxyethylene ether;
[0011] The binder is preferably at least one of ammonium polyacrylate, polyvinyl alcohol, polymethyl methacrylate, carboxymethyl cellulose, sodium alginate, and polyethylene oxide;
[0012] The mass ratio of the stabilized zirconia powder, dispersant, antistatic agent and binder is (87-115):(0.5-5):(0.5-10):(1.0-10), preferably (90-105):(1-3):(1-3):(1-3).
[0013] In some embodiments of the present invention, the zirconium oxide composite powder also includes a colorant. In the zirconium oxide composite powder, the mass ratio of the stabilized zirconium oxide powder, colorant, dispersant, antistatic agent, and binder is (87-115):(0.01-10):(0.5-5):(0.5-10):(1.0-10), preferably (90-105):(0.01-5):(1-3):(1-3):(1-3).
[0014] In some embodiments of the present invention, the zirconium oxide composite powder has at least one of the following characteristics:
[0015] The bulk density is 1~1.6g / cm 3 The powder fluidity is 40-120s and the particle size D50 is 40-80μm.
[0016] In some embodiments of the present invention, the colorant is at least one of chlorides, oxides or nitrates of iron, manganese, neodymium, cobalt, praseodymium and cerium; and the particle size D50 of the oxides of iron, manganese, neodymium, cobalt, praseodymium and cerium is 0 to 10 μm.
[0017] In some embodiments of the present invention, the particle size D50 of the zirconium oxide is 30-150 μm.
[0018] In some embodiments of the present invention, the zirconium oxide composite powder has at least one of the following characteristics:
[0019] The sphericity ratio of the zirconium oxide composite powder is greater than 95%;
[0020] The hollowness ratio of the zirconium oxide composite powder is less than 10%;
[0021] The color difference ΔE of the zirconium oxide composite powder is less than 0.5.
[0022] In order to achieve the above object, the present invention also provides the following technical solutions:
[0023] A method for preparing the above-mentioned zirconium oxide composite powder, the method comprising the following steps:
[0024] S1, providing stabilized zirconium oxide powder and additives;
[0025] S2, diluting the dispersant, antistatic agent and binder in the auxiliary agent with a diluent;
[0026] S3, mixing the stabilized zirconia powder, the diluted dispersant, antistatic agent, binder and water to obtain a slurry;
[0027] S4, drying the slurry to obtain the zirconium oxide composite powder.
[0028] In some embodiments of the present invention, the stabilized zirconium oxide powder is obtained by the following method:
[0029] A1, mixing zirconium nitrate and water to obtain a zirconium nitrate aqueous solution;
[0030] A2, adding a stabilizer to the zirconium nitrate aqueous solution obtained in step A1, and performing a synthesis reaction;
[0031] A3, filter-pressing and calcining the solution obtained in step A2 to obtain the stabilized zirconium oxide powder.
[0032] Some embodiments of the present invention include at least one of the following features:
[0033] In the step A1, the mass ratio of the zirconium nitrate to water is 1:(1-10);
[0034] In the step A2, the zirconium nitrate and the stabilizer are kept at 100 to 170° C. and reacted for 5 to 70 hours;
[0035] In the step A3, the solution obtained in the step A2 is filtered under a pressure of 0.1 to 5 MPa, the calcination temperature is 800 to 1300° C., and the insulation time is 2 to 10 hours.
[0036] In some embodiments of the present invention, the diluent is at least one of alcohols, ketones, ethers, esters, and water.
[0037] Some embodiments of the present invention have at least one of the following features:
[0038] In the step S2, the mass ratio of the dispersant to the diluent is 1:(5-15);
[0039] In the step S2, the mass ratio of the antistatic agent to the diluent is 1:(5-15);
[0040] In the step S2, the mass ratio of the binder to the diluent is 1:(5-15).
[0041] In some embodiments of the present invention, in step S3, the mass ratio of the stabilized zirconia powder, the diluted dispersant, the diluted antistatic agent, the diluted binder, and water is (87-115):(5-50):(5-100):(1-100):(200-250);
[0042] And / or, in step S3, the mixing rate is 30-90 rpm and the mixing time is 2-10 h.
[0043] In some embodiments of the present invention, the step S1 further provides a colorant;
[0044] S3, mixing the stabilized zirconia powder, the colorant, the diluted dispersant, the antistatic agent, the binder and water to obtain a slurry;
[0045] The mass ratio of the zirconium oxide, stabilizer, colorant, diluted dispersant, diluted antistatic agent, diluted binder and water is (87-115):(0.01-10):(5-50):(5-100):(1-100):(200-250).
[0046] In some embodiments of the present invention, in step S4, the drying method is one of rotary flash evaporation, high-speed centrifugal spraying, paddle drying, boiling drying, or a combination of at least two thereof.
[0047] In some embodiments of the present invention, in step S4, the slurry is dried by high-speed centrifugal spraying, wherein:
[0048] The initial temperature is 180-280°C, preferably 200-250°C;
[0049] The end temperature is 100-150°C, preferably 100-120°C;
[0050] The operating frequency of the granulating part of the drying equipment is 5000-15000rpm, preferably 8000-12000rpm, and the moisture content is controlled to be 0-1.0%, preferably 0.2-0.8%;
[0051] The particle size D50 of the zirconium oxide composite powder produced by granulation is 20 to 100 μm, preferably 40 to 80 μm.
[0052] In order to achieve the above object, the present invention also provides the following technical solutions:
[0053] A dental restoration is made of the above-mentioned zirconium oxide composite powder, or made of the zirconium oxide composite powder obtained by the above-mentioned method.
[0054] In order to achieve the above object, the present invention also provides the following technical solutions:
[0055] A method for the above dental restoration, the method comprising the following steps:
[0056] A10, powder dry pressing: placing the zirconium oxide composite powder into a dry pressing machine mold for pressing;
[0057] A20, cold isostatic pressing: the compressed zirconium oxide composite powder obtained in step A10 is sealed in plastic and placed in a cold isostatic press to pressurize and exhaust;
[0058] A30, bisque sintering and debinding: heating the zirconia composite powder obtained in step A20 and being cooled and isostatically pressed;
[0059] A40, final firing of porcelain: firing the bisque-fired zirconium oxide composite powder obtained in step A30 to obtain a bisque;
[0060] A50, post-processing: polishing, glazing and reshaping the blank obtained in step A40 to obtain the dental restoration.
[0061] Some embodiments of the present invention have at least one of the following features:
[0062] In the step A10, at least two of the zirconium oxide composite powders are mixed and then placed in the dry pressing mold for pressing, wherein at least one of the zirconium oxide composite powders does not contain a colorant, and at least one of the zirconium oxide composite powders contains a colorant;
[0063] In the step A10, the pressing pressure is 15-25 MPa;
[0064] In the step A20, the cold isostatic pressure is 180-250 MPa;
[0065] In the step A30, the heating temperature is 1000-1100° C.;
[0066] In the step A40, the firing temperature is 1400-1500°C.
[0067] In some embodiments of the present invention, there is a step A35 between step A30 and step A40, and step A35 is engraving: engraving the bisque-fired zirconium oxide composite powder obtained in step A30;
[0068] Furthermore, in the step A40, the engraved zirconium oxide composite powder obtained in the step A35 is fired to obtain the green blank.
[0069] Further areas of applicability will become apparent from the description provided in the present disclosure.
[0070] The description and specific examples in this summary are intended for purposes of illustration only and are not intended to limit the scope of the present disclosure.
[0071] Compared with the prior art, the technical solution provided by the present invention has the following beneficial effects:
[0072] The present invention provides a zirconium oxide composite powder, a dental restoration and a preparation method thereof, which can improve the mixing uniformity between a zirconium oxide composite powder without a colorant and having a color that is nearly pure white and a zirconium oxide composite powder containing a colorant and having a color, thereby improving the fluidity of zirconium oxide powders with different colors used for making dental restorations, thereby obtaining a dental restoration with better color uniformity and higher strength after porcelain formation; wherein, the present invention first prepares the zirconium oxide raw material powder into a slurry form, then adds a dispersant, an antistatic agent and a binder into the slurry, fully mixes the slurry and then dries and pulverizes the slurry to obtain a zirconium oxide composite powder without a colorant and having a color that is nearly pure white; the present invention can also add a colorant into the slurry to obtain a zirconium oxide composite powder containing a colorant and having a color; when used, the two zirconium oxide composite powders of different colors are mixed and used, and the two zirconium oxide composite powders show better fluidity, thereby obtaining a dental restoration with better color uniformity and better strength after porcelain formation in a subsequent processing process. BRIEF DESCRIPTION OF THE DRAWINGS
[0073] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some implementation plans of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without paying any creative work.
[0074] Figure 1 A flowchart of a method for preparing zirconium oxide composite powder provided in one embodiment of the present invention;
[0075] Figure 2 A flowchart of a method for preparing a dental restoration provided in another embodiment of the present invention. DETAILED DESCRIPTION
[0076] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by those skilled in the art without creative work belong to the scope of protection of the present invention. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0077] Any specific numerical value disclosed herein (including the endpoint of the numerical range) is not limited to the exact value of the numerical value, but should be understood to also cover values close to the exact value, such as all possible numerical values within the range of ±5% of the exact value. In addition, for the disclosed numerical range, the endpoint values of the range, the endpoint values and the specific point values in the range, and the specific point values can be arbitrarily combined to obtain one or more new numerical ranges, and these new numerical ranges should also be regarded as specifically disclosed herein.
[0078] The terms used in the present disclosure are only intended to describe specific exemplary embodiments and are not intended to be limiting. Unless the context clearly indicates otherwise, the singular forms "one", "a kind of" and "the" as used in the present disclosure may be intended to also include plural forms. The terms "comprise", "include", "contain" and "have" are inclusive, thus illustrating the presence of the features, elements, compositions, steps, integers, operations and / or components, but do not exclude the presence or addition of one or more other features, integers, steps, operations, elements, components and / or their collections. Although the open term "comprise" should be understood as a non-limiting term for describing and claiming the various embodiments described in the present disclosure, in some aspects, the term may be alternatively understood as a more restrictive and limited term, such as "consisting of..." or "consisting essentially of..." Thus, for any given embodiment of a narration composition, material, component, element, feature, integer, operation and / or process step, the present disclosure also particularly includes an embodiment consisting of or essentially consisting of such a composition, material, component, element, feature, integer, operation and / or process step. In the case of “consisting of,” alternative embodiments exclude any additional compositions, materials, components, elements, features, integers, operations and / or process steps, while in the case of “consisting essentially of,” any additional compositions, materials, components, elements, features, integers, operations and / or process steps that materially affect the basic and novel characteristics are excluded from such embodiments, but any compositions, materials, components, elements, features, integers, operations and / or process steps that do not materially affect the basic and novel characteristics may be included in the embodiments.
[0079] Any method steps, processes, and operations described in the present disclosure should not be construed as necessarily requiring their performance in the particular order discussed or illustrated, unless expressly identified as a certain order of performance. It should also be understood that additional or alternative steps may be used unless otherwise stated.
[0080] In this application, except for the contents explicitly described, any matters or items not mentioned are directly applicable to those known in the art without any changes. Moreover, any embodiment described in this disclosure can be freely combined with one or more other embodiments described in this disclosure, and the technical solutions or technical ideas formed thereby are regarded as part of the original disclosure or original record of this application, and should not be regarded as new contents that have not been disclosed or anticipated in this disclosure, unless a person skilled in the art considers that the combination is obviously unreasonable.
[0081] Unless otherwise specified, the terms used herein have the same meaning as commonly understood by those skilled in the art. If a term is defined herein and its definition is different from the commonly understood meaning in the art, the definition herein shall prevail.
[0082] Unless otherwise stated, when % is mentioned herein, it means wt. %.
[0083] First aspect
[0084] The invention provides a zirconium oxide composite powder, which comprises zirconium oxide, a stabilizer and an auxiliary agent; wherein the auxiliary agent comprises: a dispersant, preferably at least one of propylene glycol methyl ether, sodium polymethacrylate, polyacrylamide, sodium oleate, polyethylene ether, sodium hexametaphosphate and sodium tripolyphosphate, and an ether dispersant can improve the wettability of the surface of solid particles, so that the particles are more easily wetted and dispersed by liquid; an ionic polymer dispersant has both charge effect and steric hindrance effect, and after being adsorbed on the surface of solid particles, the particles are charged with the same charge, and the particles are kept in a dispersed state due to charge repulsion; at the same time, the polymer chains adsorbed on the surface of the solid particles prevent the particles from approaching and agglomerating each other through steric hindrance, thereby improving the stability of the dispersed system; an antistatic agent, preferably at least one of glycerol fatty acid ester, lauryl alcohol, dodecanol, n-octanol, glycerol, polyethylene glycol, diethylene glycol methyl ether and octadecylamine polyoxyethylene ether, and the antistatic agent is mainly alcohols and ethers, and contains hydrophilic groups and lipophilic groups. During the drying process, the hydrophilic group will absorb moisture in the air and also play a hydrogen bonding role, forming a thin conductive layer on the surface of the particles. Static charge can be conducted through this conductive layer, reducing static electricity and improving the smoothness of the granulated balls. The binder is preferably at least one of ammonium polyacrylate, polyvinyl alcohol, polymethyl methacrylate, carboxymethyl cellulose, sodium alginate, and polyethylene oxide. The key consideration in the selection of the binder is that it cannot react with the dispersant and antistatic agent, and can adhere the primary particles together during the granulation process through hydrogen bonds, van der Waals forces, ionic bonds, covalent bonds, etc., and the polymer is mostly based on CC "hard segments", which also plays a supporting role in the granulation process and reduces the proportion of ball collapse.
[0085] Adding a dispersant improves the hydrophilicity of the primary particles after slurry grinding and reduces the inherent agglomerates in the grinding process; in some embodiments of the present invention, after dispersion, the Zeta potential of the dispersed system changes from 0 to 100 mV to -100 to 0 mV, and the particle size distribution D50 of the primary particles after dispersion is 0.10 to 0.50 μm.
[0086] Antistatic agents are added to the slurry dispersion system to reduce static electricity generated by friction between granulation balls and equipment, which affects the surface smoothness of the particles. Binders are added to the slurry dispersion system to improve the support of the original particles in the process of drying to become larger particles, so that large particles with high sphericity, high gloss and low proportion of local depressions are obtained.
[0087] It is worth noting that the present invention improves the fluidity of the obtained zirconium oxide composite powder by the above-mentioned scheme of "adding dispersants, antistatic agents and binders to the slurry system to modify the surface of zirconium oxide", which can improve the mixing uniformity between the zirconium oxide composite powder obtained by the present invention and the subsequent color composite powder used to match it, thereby obtaining a dental restoration with better color uniformity and higher strength after porcelain formation.
[0088] In some embodiments of the present invention, the mass ratio of zirconium oxide, stabilizer, dispersant, antistatic agent and binder is (87-115):(0.5-5):(0.5-10):(1.0-10), preferably (90-105):(1-3):(1-3):(1-3).
[0089] In some embodiments of the present invention, the zirconium oxide composite powder also includes a colorant. In the zirconium oxide composite powder, the mass ratio of the zirconium oxide, stabilizer, colorant, dispersant, antistatic agent, and binder is (87-115):(0.01-10):(0.5-5):(0.5-10):(1.0-10), preferably (90-105):(0.01-5):(1-3):(1-3):(1-3).
[0090] It is worth noting that the zirconium oxide composite powder obtained in some embodiments of the present invention does not contain a colorant, so the color is white or close to white. The white zirconium oxide composite powder can be subsequently mixed with a matching colored composite powder to make a dental restoration; while the zirconium oxide composite powder obtained in other embodiments contains a colorant, so the zirconium oxide composite powder is not pure white, but can also be subsequently mixed with a matching colored composite powder to make a dental restoration.
[0091] It should be noted that some embodiments of the present invention provide a zirconium oxide composite powder, which can improve the mixing uniformity between zirconium oxide composite powder without colorant and nearly pure white color and zirconium oxide composite powder with colorant, thereby improving the fluidity of zirconium oxide powder with different colors used to make dental restorations, thereby obtaining dental restorations with better color uniformity and higher strength after porcelain formation; wherein, the present invention first prepares the zirconium oxide raw material powder into a slurry form, then adds a dispersant, an antistatic agent and a binder to the slurry, and then dries and pulverizes after fully mixing, thereby obtaining a zirconium oxide composite powder without colorant and nearly pure white color. In other embodiments of the present invention, a colorant can also be added to the slurry to obtain a zirconium oxide composite powder with colorant. When used, the two zirconium oxide composite powders of different colors are mixed and used, and the two zirconium oxide composite powders show better fluidity, thereby obtaining a dental restoration with better color uniformity and better strength after porcelain formation in the subsequent processing process.
[0092] In some embodiments of the present invention, the bulk density of the zirconium oxide composite powder is 1 to 1.6 g / cm 3 ; Exemplarily, it can be 1.2g / cm 3 or 1.5g / cm 3 .
[0093] In some embodiments of the present invention, the powder fluidity of the zirconium oxide composite powder is 40 to 120 seconds, and illustratively may be 80 seconds or 120 seconds.
[0094] In some embodiments of the present invention, the particle size D50 of the zirconium oxide composite powder is 40-80 μm, and can be 50 μm or 75 μm by way of example.
[0095] It is worth noting that the zirconium oxide composite powder obtained in some embodiments of the present invention, whether or not it contains a colorant, can have a bulk density of 1 to 1.6 g / cm 3 , its powder fluidity can be 40-120s, and its D50 can be 40-80μm. In this way, the zirconium oxide colored powder provided by the present invention and the color composite powder can have consistent particle sizes, so that the two exhibit better fluidity when mixed, which is conducive to obtaining a dental restoration with more uniform material and better overall performance.
[0096] In some embodiments of the present invention, the stabilizer is at least one of nitrates or chlorides of yttrium, erbium, silicon, magnesium, and calcium. It is worth noting that the nitrate or chloride can be fully dissolved in the aqueous solution. It is worth noting that the content of the stabilizer does not mean that the stabilizer is directly present in the zirconium oxide composite powder as a separate substance. In fact, the stabilizer can be present in combination with zirconium oxide, for example in the form of zirconium oxide stabilized by the stabilizer.
[0097] Preferably, in some embodiments of the present invention, only yttrium nitrate is used as the stabilizer; it is worth noting that the specific mechanism of action of yttrium is as follows: 1. Limiting the transition between zirconium oxide crystal forms, forming a solid solution or complex with zirconium oxide during the calcination process, and existing in the form of yttrium oxide (chemical formula Y2O3). ; 2. At room temperature, zirconium oxide is a monoclinic phase, which is an extremely unstable phase and cannot be applied to products; at high temperatures, the monoclinic phase will transform into a tetragonal phase, which is a stable phase with good chemical stability, but when the temperature drops to room temperature, it will transform from tetragonal to monoclinic, which is an unstable state. The role of yttrium is to form a solid solution or complex with zirconium oxide at high temperatures, limiting the transition from tetragonal to monoclinic during the cooling process, so that when it is reduced to room temperature, most of the tetragonal phase will be retained, and it will be stable at room temperature; 3. Within a certain range. The more Y content, the lower the monoclinic phase ratio, the higher the tetragonal phase ratio, the more stable the performance of the dental restoration and the better the light transmittance.
[0098] In some embodiments of the present invention, the colorant is at least one of chlorides, oxides or nitrates of iron, manganese, neodymium, cobalt, praseodymium or cerium.
[0099] In some embodiments of the present invention, the particle size D50 of the zirconium oxide is 30-150 μm, and illustratively may be 80 μm or 120 μm.
[0100] In some embodiments of the present invention, the sphericity ratio of the zirconium oxide composite powder is greater than 95%, and can be 96% or 99% by way of example. It is worth noting that the higher the sphericity ratio, the better the fluidity of the obtained zirconium oxide composite powder.
[0101] In some embodiments of the present invention, the hollowness ratio of the zirconium oxide composite powder is less than 10%, and can be 2% or 5% by way of example. It is worth noting that the lower the hollowness, the better the fluidity of the obtained zirconium oxide composite powder.
[0102] In some embodiments of the present invention, the color difference of the zirconium oxide composite powder is ΔE<0.5, and ΔE=0.1 or ΔE=0.2. It is worth noting that the smaller the ΔE, the better the color uniformity of the obtained zirconium oxide composite powder.
[0103] The present invention significantly improves the dispersion state of primary particles and reduces the generation of agglomerates in the sand grinding process by adding a dispersant to the slurry after beating and grinding, so that the primary particles have good fluidity. In the drying process, zirconium oxide composite powder with excellent fluidity is prepared. The sphericity ratio of the powder is greater than 95%, the hollowness ratio is less than 10%, and the color powder made from the inferior powder has an intra-batch ΔE extreme difference of less than 0.5, and has good intra-batch uniformity.
[0104] The present invention significantly reduces the problems of poor surface finish of particles and adhesion of large and small particles caused by electrostatic effects during the drying process by adding an antistatic agent to the slurry after beating and grinding, and adjusting the parameters of the drying equipment. The fluidity of the finished powder can reach 40 to 120 seconds. Good fluidity reduces the internal defects of the powder during the molding and pressing process, and the strength mean and range are significantly improved. Taking the zirconium oxide product with a stabilizer content of 6.0 to 10.0% as an example, the strength (yttrium content: 6.0 to 10.0%) is >850MPa, and the range of strength of 10 splines is <200MPa. It is worth noting that the so-called "extreme range of strength of 10 splines" means: making 10 splines, measuring their three-point bending strength respectively, taking the average value of the three-point bending strength of these 10 splines, and then evaluating the difference between the maximum and minimum values of these 10 splines.
[0105] Second aspect
[0106] The present invention provides a method for preparing the above-mentioned zirconium oxide composite powder, which comprises the following steps: S1, providing stabilized zirconium oxide powder and additives; S2, diluting the dispersant, antistatic agent and binder in the additives with a diluent; S3, mixing the stabilized zirconium oxide powder, the diluted dispersant, antistatic agent, binder and water to obtain a slurry; S4, drying the slurry to obtain the zirconium oxide composite powder.
[0107] It is worth noting that in step S1 of the above method provided by the present invention, the zirconium oxide used can be made by any method, and illustratively the zirconium oxide raw material can be obtained by hydrothermal synthesis or calcination; the above method provided by the present invention aims to perform secondary modification on the zirconium oxide raw material to obtain a zirconium oxide composite powder with better fluidity, and further a dental restoration with better color uniformity and overall strength.
[0108] It is understandable that if the dispersant, antistatic agent and binder are directly mixed with the stabilized zirconia powder without going through the dilution operation of the above-mentioned step S2, problems such as caking and agglomeration may occur, which is not conducive to the mixing of the substances and, in turn, is not conducive to the surface modification of the stabilized zirconia powder. Therefore, it is necessary to first dilute and dissolve the dispersant, antistatic agent and binder with a diluent, and then make a slurry, so as to facilitate the surface modification of the zirconia powder in the slurry system.
[0109] In some embodiments of the present invention, the stabilized zirconium oxide powder is obtained by the following method:
[0110] A1, mixing zirconium nitrate and water to obtain a zirconium nitrate aqueous solution;
[0111] A2, adding a stabilizer to the zirconium nitrate aqueous solution obtained in step A1, and performing a synthesis reaction;
[0112] A3, filter-pressing and calcining the solution obtained in step A2 to obtain the stabilized zirconium oxide powder.
[0113] In some embodiments of the present invention, in step A1, the mass ratio of zirconium nitrate to water is 1:(1-10).
[0114] In some embodiments of the present invention, in step A2, the zirconium nitrate and the stabilizer are kept at 100-170° C. for 5-70 hours.
[0115] In some embodiments of the present invention, in step A3, the solution obtained in step A2 is filter-filtered at a pressure of 0.1 to 5 MPa, a calcination temperature of 800 to 1300° C., and a heat preservation time of 2 to 10 h.
[0116] In some embodiments of the present invention, the diluent is at least one of alcohols, ketones, ethers, esters, and water.
[0117] In some embodiments of the present invention, in step S2, the mass ratio of the dispersant to the diluent is 1:(5-15); illustratively, it can be 1:6 or 1:12. In some embodiments of the present invention, after dispersion, the Zeta potential of the dispersed system changes from 0-100mV to -100-0mV, and the primary particle size distribution D50 after dispersion is 0.10-0.50μm, which is conducive to improving the surface properties of zirconium oxide and making it have better fluidity.
[0118] In some embodiments of the present invention, in step S2, the mass ratio of the antistatic agent to the diluent is 1:(5-15); illustratively, it can be 1:8 or 1:13. It is understood that adding an antistatic agent to the modified slurry system can reduce static electricity generated by friction between powder particles and between powder particles and equipment, which affects the surface finish of the particles.
[0119] In some embodiments of the present invention, in step S2, the mass ratio of the binder to the diluent is 1:(5-15); illustratively, it can be 1:6 or 1:11. It is understood that the addition of the binder can increase the size of the zirconium oxide primary particles after drying, and provide sufficient support for the large particle powder to prevent the large particles from breaking, so as to obtain large particles with high sphericity, high gloss, and low local depression ratio.
[0120] In some embodiments of the present invention, in step S3, the mass ratio of the zirconium oxide, stabilizer, diluted dispersant, diluted antistatic agent, diluted binder, and water is (85-100):(2-15):(5-50):(5-100):(1-100):(200-250).
[0121] In some embodiments of the present invention, in step S3, the mixing rate is 30-90 rpm, and the mixing time is 2-10 h; illustratively, the mixing rate may be 40 rpm or 70 rpm, and the mixing time may be 3 h or 8 h.
[0122] In some embodiments of the present invention, the step S1 also provides a colorant; S3, mix the stabilized zirconia powder, colorant, diluted dispersant, antistatic agent, binder and water to obtain a slurry; the mass ratio of the stabilized zirconia powder, colorant, diluted dispersant, diluted antistatic agent, diluted binder and water is (87~115):(0.01~10):(5~50):(5~100):(1~100):(200~250).
[0123] In some embodiments of the present invention, in step S4, the drying method is one of rotary flash evaporation, high-speed centrifugal spraying, paddle drying, boiling drying, or a combination of at least two thereof.
[0124] In some embodiments of the present invention, in step S4, the slurry is dried by high-speed centrifugal spraying, wherein: the initial temperature is 180-280°C, preferably 200-250°C; the end temperature is 100-150°C, preferably 100-120°C; the operating frequency of the granulation component of the drying equipment is 5000-15000rpm, preferably 8000-12000rpm, and the moisture content is controlled to 0-1.0%, preferably 0.2-0.8%; the particle size D50 of the zirconium oxide composite powder produced by granulation is 20-100μm, preferably 40-80μm.
[0125] It is worth noting that the "drying equipment granulation component" in the specification of the present invention refers to: the drying granulation equipment used in some embodiments has two functions of drying and granulation and powder making; in some embodiments, the equipment dries first and then granulates and powders; in other embodiments, granulation and powder making can be performed during the drying process.
[0126] In some embodiments of the present invention, 0.5-5.0% dispersant is added to the grinding slurry to improve the hydrophilicity of the primary particles, reduce the inherent agglomerates of the primary particles in the grinding process, and change the Zeta potential of the slurry dispersion system, so that the slurry has better fluidity and lower viscosity; during the drying process, the moisture of the particles evaporates from the center to the outside, negative pressure is formed in the center, and the particles shrink. The high-fluidity primary particles will reduce the probability of the occurrence of hollow balls, shriveled balls, and fine particles. According to this process, the sphericity ratio of the powder output is >95%, and the hollowness ratio is <10%.
[0127] In some embodiments of the present invention, 0 to 10% antistatic agent is added to the grinding slurry to reduce static electricity generated by friction between particles and between particles and equipment during the drying process, which affects the surface smoothness of the particles and reduces the sticky particles caused by static electricity. The fluidity of the finished powder can reach 40 to 120 seconds.
[0128] The inventors of the present invention found that when no auxiliary molding aid is added to the grinding slurry, the powder fluidity is greater than 200s, the bridging phenomenon between the powders is serious, the Hall flow meter is blocked, and there is almost no fluidity; when the powder fluidity is 120-200s, it affects the uniformity of mixing with other colored powders, resulting in poor color uniformity after sintering of the denture; during the tooth cake pressing process, internal defects of the tooth cake will be caused due to the inability to effectively fill the mold, and the porcelain strength will be significantly reduced.
[0129] In addition, the inventors of the present invention found that when the powder fluidity is <40s, the powder state at this time has an increased density and is more inclined to form "solid" particles, but the powder activity is significantly reduced; the powder loses its adhesiveness during the pressing process, is difficult to shape, and no longer has the characteristics of a dental material.
[0130] The third aspect
[0131] The present invention also provides a dental restoration, which is made of the above-mentioned zirconium oxide composite powder, or made of the zirconium oxide composite powder obtained by the above-mentioned method.
[0132] The fourth aspect
[0133] The present invention also provides a method for the above-mentioned dental restoration, which comprises the following steps: A10, powder dry pressing molding: placing the zirconium oxide composite powder into a dry pressing machine mold for pressing; A20, cold isostatic pressing: sealing the compressed zirconium oxide composite powder obtained in step A10, placing it into a cold isostatic press for pressurization and exhaust; A30, bisque firing and debinding: heating the cold isostatically pressed zirconium oxide composite powder obtained in step A20; A40, final firing and porcelainization: firing the bisque fired zirconium oxide composite powder obtained in step A30 to obtain a bisque blank; A50, post-processing: polishing, glazing and shaping the bisque blank obtained in step A40 to obtain the dental restoration.
[0134] In some embodiments of the present invention, in step A10, at least two of the zirconia composite powders are mixed and then placed in the dry pressing mold for pressing, wherein at least one of the zirconia composite powders does not contain a colorant, and at least one of the zirconia composite powders contains a colorant. It is understandable that the present invention mixes at least two zirconia composite powders of different colors, wherein at least one zirconia composite powder is nearly white, and the remaining zirconia composite powders contain a colorant and are colored, and these zirconia composite powders exhibit better fluidity, thereby obtaining a dental restoration with better color uniformity and better strength after porcelainization in the subsequent processing process.
[0135] In some embodiments of the present invention, in step A10, the pressing pressure is 15-25 MPa, and illustratively may be 18 MPa or 20 MPa.
[0136] In some embodiments of the present invention, in step A20, the cold isostatic pressure is 180-250 MPa, and illustratively may be 200 MPa or 230 MPa.
[0137] In some embodiments of the present invention, in step A30, the heating temperature is 1000-1100°C, and illustratively may be 1030°C or 1075°C.
[0138] In some embodiments of the present invention, in step A40, the firing temperature is 1400-1500°C, and illustratively may be 1430°C or 1475°C.
[0139] In some embodiments of the present invention, there is a step A35 between step A30 and step A40, and step A35 is carving: carving is performed on the bisque-fired zirconium oxide composite powder obtained in step A30; and in step A40, the carved zirconium oxide composite powder obtained in step A35 is fired to obtain the bisque.
[0140] Example
[0141] Preparation of stabilized zirconia powder
[0142] First, the raw materials zirconium nitrate and water are mixed in a mass ratio of 1:5, and then yttrium nitrate is added to the reaction solution, wherein the mass ratio of yttrium nitrate to zirconium nitrate is (0.065-0.130):1, and the temperature is gradually raised to 160°C, kept warm for 50 hours for synthesis reaction, and high-temperature calcination is carried out, and kept warm at 950°C for 6 hours to obtain stabilized zirconium oxide powder. The stabilized zirconium oxide powder is used in all the following examples and comparative examples, and the specific mass ratio of zirconium oxide and yttrium oxide is shown in Tables 1-6 below.
[0143] In addition, the stable tetragonal phase is formed by high-temperature sintering followed by cooling, allowing yttrium and zirconium to form a solid solution phase.
[0144] Example 1
[0145] This embodiment sequentially prepares the above-mentioned zirconium oxide composite powder and dental restoration according to the following steps:
[0146] B1, providing stabilized zirconia powder, dispersant, antistatic agent and binder, wherein the stabilized zirconia powder, dispersant, antistatic agent and binder are in a mass ratio of 91:0.5:0.5:1.0, the dispersant is sodium polymethacrylate, the antistatic agent is polyethylene glycol, and the binder is polyvinyl alcohol;
[0147] B2, diluting the above-mentioned dispersant, antistatic agent and binder with a diluent, wherein the mass ratio of the dispersant to the diluent is 1:5, the mass ratio of the antistatic agent to the diluent is 1:5, and the mass ratio of the binder to the diluent is 1:15;
[0148] B3, mixing the above materials to obtain a slurry, wherein the rotation speed of the mixing process is 30 rpm and the mixing time is 2.5 h;
[0149] B4, drying the slurry by high-speed centrifugal spraying to obtain the zirconium oxide composite powder, wherein the initial temperature is 250° C., the end temperature is 120° C., the operating frequency of the granulation part of the drying equipment is 7000 rpm, the moisture content is controlled to 0.92%, and the granulation particle size D50 is 86 μm;
[0150] B5, the mass ratio of zirconium oxide to yttrium oxide in the zirconium oxide composite powder is 85:6.0, and the zirconium oxide composite powder is pressed at a pressing pressure of 20 MPa to form a shape;
[0151] B6, plastic sealing is performed using a cold isostatic pressure of 250 MPa, and the product is placed in a cold isostatic press for pressurized exhaust;
[0152] B7, bisque firing and debinding at 980°C;
[0153] B8, engraving;
[0154] B9, finally fired at 1450℃ to form porcelain;
[0155] B10, polishing, glazing and reshaping the blank obtained in step B9 to obtain the dental restoration.
[0156] It is worth noting that the color difference of the composite powder obtained in Example 1 after being made into a dental restoration is 0, there is no color difference, and the color is uniform by default.
[0157] Example 2
[0158] This embodiment sequentially prepares the above-mentioned zirconium oxide composite powder and dental restoration according to the following steps:
[0159] B1, providing stabilized zirconium oxide powder, a colorant, a dispersant, an antistatic agent and a binder, wherein the mass ratio of the stabilized zirconium oxide, the colorant, the dispersant, the antistatic agent and the binder is 93.3:0.3:1.0:1.5:3.0, the colorant is manganese oxide, the dispersant is sodium polymethacrylate, the antistatic agent is polyethylene glycol, and the binder is polyvinyl alcohol;
[0160] B2, diluting the above-mentioned dispersant, antistatic agent and binder with a diluent, wherein the mass ratio of the dispersant to the diluent is 1:7, the mass ratio of the antistatic agent to the diluent is 1:10, and the mass ratio of the binder to the diluent is 1:13;
[0161] B3, mixing the above materials to obtain a slurry, wherein the rotation speed of the mixing process is 40 rpm and the mixing time is 3.5 h;
[0162] B4, drying the slurry by high-speed centrifugal spraying to obtain the zirconium oxide composite powder, wherein the initial temperature is 250° C., the end temperature is 120° C., the operating frequency of the granulation part of the drying equipment is 8000 rpm, the moisture content is controlled to 0.85%, and the granulation particle size D50 is 75 μm;
[0163] B5, the mass ratio of zirconium oxide to yttrium oxide in the zirconium oxide composite powder obtained in this embodiment is 87:6.3, the zirconium oxide composite powder obtained in Example 1 and the composite powder obtained in this embodiment are mixed in a mass ratio of 4:1, and the mixed zirconium oxide composite powder is pressed at a pressing pressure of 30 MPa to form;
[0164] B6, plastic sealing is performed using a cold isostatic pressure of 240 MPa, and the product is placed in a cold isostatic press for pressurized exhaust;
[0165] B7, bisque firing and debinding at 1000°C;
[0166] B8, engraving;
[0167] B9, finally fired at 1480℃ to form porcelain;
[0168] B10, polishing, glazing and reshaping the blank obtained in step B9 to obtain the dental restoration.
[0169] Example 3
[0170] This embodiment sequentially prepares the above-mentioned zirconium oxide composite powder and dental restoration according to the following steps:
[0171] B1, providing stabilized zirconia powder, colorant, dispersant, antistatic agent and binder, wherein the mass ratio of the stabilized zirconia powder, colorant, dispersant, antistatic agent and binder is 95.6:0.3:1.5:2.5:5.0, the colorant is neodymium oxide, the dispersant is sodium polymethacrylate, the antistatic agent is polyethylene glycol, and the binder is polyvinyl alcohol;
[0172] B2, diluting the above-mentioned dispersant, antistatic agent and binder with a diluent, wherein the mass ratio of the dispersant to the diluent is 1:9, the mass ratio of the antistatic agent to the diluent is 1:15, and the mass ratio of the binder to the diluent is 1:11;
[0173] B3, mixing the above materials to obtain a slurry, wherein the rotation speed of the mixing process is 50 rpm and the mixing time is 4.5 h;
[0174] B4, drying the slurry by high-speed centrifugal spraying to obtain the zirconium oxide composite powder, wherein the initial temperature is 250° C., the end temperature is 120° C., the operating frequency of the granulation part of the drying equipment is 9000 rpm, the moisture content is controlled to 0.78%, and the granulation particle size D50 is 69 μm;
[0175] B5, the mass ratio of zirconium oxide to yttrium oxide in the zirconium oxide composite powder obtained in this embodiment is 89:6.6, the zirconium oxide composite powder obtained in Example 1 and the composite powder obtained in this embodiment are mixed in a mass ratio of 4:1, and the mixed zirconium oxide composite powder is pressed at a pressing pressure of 40 MPa to form;
[0176] B6, plastic sealing is performed using a cold isostatic pressure of 220 MPa, and the product is placed in a cold isostatic press for pressurized exhaust;
[0177] B7, bisque firing and debinding at 1030°C;
[0178] B8, engraving;
[0179] B9, finally fired at 1500℃ to form porcelain;
[0180] B10, polishing, glazing and reshaping the blank obtained in step B9 to obtain the dental restoration.
[0181] Example 4
[0182] This embodiment sequentially prepares the above-mentioned zirconium oxide composite powder and dental restoration according to the following steps:
[0183] B1, providing stabilized zirconia powder, colorant, dispersant, antistatic agent and binder, wherein the mass ratio of the stabilized zirconia powder, colorant, dispersant, antistatic agent and binder is 97.9:0.3:2.0:3.5:7.0, the colorant is cobalt oxide, the dispersant is sodium polymethacrylate, the antistatic agent is polyethylene glycol, and the binder is ammonium polyacrylate;
[0184] B2, diluting the above-mentioned dispersant, antistatic agent and binder with a diluent, wherein the mass ratio of the dispersant to the diluent is 1:11, the mass ratio of the antistatic agent to the diluent is 1:5, and the mass ratio of the binder to the diluent is 1:9;
[0185] B3, mixing the above materials to obtain a slurry, wherein the rotation speed of the mixing process is 60 rpm and the mixing time is 5.5 h;
[0186] B4, drying the slurry by high-speed centrifugal spraying to obtain the zirconium oxide composite powder, wherein the initial temperature is 250°C, the end temperature is 120°C, the operating frequency of the granulation part of the drying equipment is 10000rpm, the moisture content is controlled to 0.66%, and the granulation particle size D50 is 57μm;
[0187] B5, the mass ratio of zirconium oxide to yttrium oxide in the zirconium oxide composite powder obtained in this embodiment is 91:6.9, the zirconium oxide composite powder obtained in Example 1 and the composite powder obtained in this embodiment are mixed in a mass ratio of 4:1, and the mixed zirconium oxide composite powder is pressed at a pressing pressure of 60 MPa to form;
[0188] B6, plastic sealing is performed using a cold isostatic pressure of 200 MPa, and the product is placed in a cold isostatic press for pressurized exhaust;
[0189] B7, bisque firing and debinding at 1050°C;
[0190] B8, engraving;
[0191] B9, finally fired at 1510℃ to form porcelain;
[0192] B10, polishing, glazing and reshaping the blank obtained in step B9 to obtain the dental restoration.
[0193] Example 5
[0194] This embodiment sequentially prepares the above-mentioned zirconium oxide composite powder and dental restoration according to the following steps:
[0195] B1, providing stabilized zirconia powder, colorant, dispersant, antistatic agent and binder, wherein the mass ratio of the stabilized zirconia powder, colorant, dispersant, antistatic agent and binder is 100.4:0.3:2.5:4.5:9.0, the colorant is praseodymium oxide, the dispersant is polyacrylamide, the antistatic agent is polyethylene glycol, and the binder is ammonium polyacrylate;
[0196] B2, diluting the above-mentioned dispersant, antistatic agent and binder with a diluent, wherein the mass ratio of the dispersant to the diluent is 1:13, the mass ratio of the antistatic agent to the diluent is 1:10, and the mass ratio of the binder to the diluent is 1:7;
[0197] B3, mixing the above materials to obtain a slurry, wherein the rotation speed of the mixing process is 70 rpm and the mixing time is 6.5 h;
[0198] B4, drying the slurry by a rotary flash evaporator to obtain the zirconium oxide composite powder, wherein the initial temperature is 250° C., the end temperature is 120° C., the operating frequency of the granulation part of the drying equipment is 10500 rpm, the moisture content is controlled to 0.57%, and the granulation particle size D50 is 48 μm;
[0199] B5, the mass ratio of zirconium oxide to yttrium oxide in the zirconium oxide composite powder obtained in this embodiment is 93:7.4, the zirconium oxide composite powder obtained in Example 1 and the composite powder obtained in this embodiment are mixed in a mass ratio of 4:1, and the mixed zirconium oxide composite powder is pressed at a pressing pressure of 80 MPa to form;
[0200] B6, plastic sealing is performed using a cold isostatic pressure of 190 MPa, and the product is placed in a cold isostatic press for pressurized exhaust;
[0201] B7, bisque firing and debinding at 1070°C;
[0202] B8, engraving;
[0203] B9, finally fired at 1530℃ to form porcelain;
[0204] B10, polishing, glazing and reshaping the blank obtained in step B9 to obtain the dental restoration.
[0205] Example 6
[0206] This embodiment sequentially prepares the above-mentioned zirconium oxide composite powder and dental restoration according to the following steps:
[0207] B1, providing stabilized zirconia powder, colorant, dispersant, antistatic agent and binder, wherein the mass ratio of the stabilized zirconia powder, colorant, dispersant, antistatic agent and binder is 102.9:0.3:3.0:5.0:2.0, the colorant is cerium oxide, the dispersant is polyacrylamide, the antistatic agent is polyethylene glycol, and the binder is ammonium polyacrylate;
[0208] B2, diluting the above-mentioned dispersant, antistatic agent and binder with a diluent, wherein the mass ratio of the dispersant to the diluent is 1:15, the mass ratio of the antistatic agent to the diluent is 1:15, and the mass ratio of the binder to the diluent is 1:5;
[0209] B3, mixing the above materials to obtain a slurry, wherein the rotation speed of the mixing process is 80 rpm and the mixing time is 7.5 h;
[0210] B4, drying the slurry by a rotary flash evaporator to obtain the zirconium oxide composite powder, wherein the initial temperature is 250° C., the end temperature is 120° C., the operating frequency of the granulation part of the drying equipment is 11000 rpm, the moisture content is controlled to 0.49%, and the granulation particle size D50 is 45 μm;
[0211] B5, the mass ratio of zirconium oxide to yttrium oxide in the zirconium oxide composite powder obtained in this embodiment is 95:7.9, the zirconium oxide composite powder obtained in Example 1 and the composite powder obtained in this embodiment are mixed in a mass ratio of 4:1, and the mixed zirconium oxide composite powder is pressed at a pressing pressure of 100 MPa to form;
[0212] B6, plastic sealing is performed using a cold isostatic pressure of 180 MPa, and the product is placed in a cold isostatic press for pressurized exhaust;
[0213] B7, bisque firing and debinding at 1090°C;
[0214] B8, engraving;
[0215] B9, finally fired at 1460℃ to form porcelain;
[0216] B10, polishing, glazing and reshaping the blank obtained in step B9 to obtain the dental restoration.
[0217] Example 7
[0218] This embodiment sequentially prepares the above-mentioned zirconium oxide composite powder and dental restoration according to the following steps:
[0219] B1, providing stabilized zirconia powder, colorant, dispersant, antistatic agent and binder, wherein the mass ratio of the stabilized zirconia powder, colorant, dispersant, antistatic agent and binder is 105.2:1.0:3.5:1.0:4.0, the colorant is a mixture of iron oxide, neodymium oxide and manganese oxide in a mass ratio of 1:0.1:0.1, the dispersant is propylene glycol methyl ether, the antistatic agent is n-octanol, and the binder is carboxymethyl cellulose;
[0220] B2, diluting the above-mentioned dispersant, antistatic agent and binder with a diluent, wherein the mass ratio of the dispersant to the diluent is 1:13, the mass ratio of the antistatic agent to the diluent is 1:5, and the mass ratio of the binder to the diluent is 1:14;
[0221] B3, mixing the above materials to obtain a slurry, wherein the rotation speed of the mixing process is 90 rpm and the mixing time is 8.5 h;
[0222] B4, drying the slurry by a rotary flash evaporator to obtain the zirconium oxide composite powder, wherein the initial temperature is 250° C., the end temperature is 120° C., the operating frequency of the granulation part of the drying equipment is 7000 rpm, the moisture content is controlled to 0.91%, and the granulation particle size D50 is 92 μm;
[0223] B5, the mass ratio of zirconium oxide to yttrium oxide in the zirconium oxide composite powder obtained in this embodiment is 97:8.2, the zirconium oxide composite powder obtained in Example 1 and the composite powder obtained in this embodiment are mixed in a mass ratio of 4:1, and the mixed zirconium oxide composite powder is pressed at a pressing pressure of 20 MPa to form;
[0224] B6, plastic sealing is performed using a cold isostatic pressure of 185 MPa, and the product is placed in a cold isostatic press for pressurized exhaust;
[0225] B7, bisque firing and debinding at 1110°C;
[0226] B8, engraving;
[0227] B9, finally fired at 1470℃ to form porcelain;
[0228] B10, polishing, glazing and reshaping the blank obtained in step B9 to obtain the dental restoration.
[0229] Example 8
[0230] This embodiment sequentially prepares the above-mentioned zirconium oxide composite powder and dental restoration according to the following steps:
[0231] B1, providing stabilized zirconia powder, colorant, dispersant, antistatic agent and binder, wherein the mass ratio of the stabilized zirconia powder, colorant, dispersant, antistatic agent and binder is 107.5:1.0:4.0:2.0:6.0, the colorant is a mixture of iron oxide, neodymium oxide and cobalt oxide in a mass ratio of 1:0.1:0.1, the dispersant is propylene glycol methyl ether, the antistatic agent is n-octanol, and the binder is carboxymethyl cellulose;
[0232] B2, diluting the above-mentioned dispersant, antistatic agent and binder with a diluent, wherein the mass ratio of the dispersant to the diluent is 1:11, the mass ratio of the antistatic agent to the diluent is 1:10, and the mass ratio of the binder to the diluent is 1:12;
[0233] B3, mixing the above materials to obtain a slurry, wherein the rotation speed of the mixing process is 35 rpm and the mixing time is 9.5 h;
[0234] B4, drying the slurry by a paddle dryer to obtain the zirconium oxide composite powder, wherein the initial temperature is 250° C., the end temperature is 120° C., the operating frequency of the granulation part of the drying equipment is 8000 rpm, the moisture content is controlled to 0.80%, and the granulation particle size D50 is 77 μm;
[0235] B5, the mass ratio of zirconium oxide to yttrium oxide in the zirconium oxide composite powder obtained in this embodiment is 99:8.5, the zirconium oxide composite powder obtained in Example 1 and the composite powder obtained in this embodiment are mixed in a mass ratio of 4:1, and the mixed zirconium oxide composite powder is pressed at a pressing pressure of 30 MPa to form;
[0236] B6, plastic sealing is performed using a cold isostatic pressure of 195 MPa, and the product is placed in a cold isostatic press for pressurized exhaust;
[0237] B7, bisque firing and debinding at 900°C;
[0238] B8, engraving;
[0239] B9, finally fired at 1490℃ to form porcelain;
[0240] B10, polishing, glazing and reshaping the blank obtained in step B9 to obtain the dental restoration.
[0241] Example 9
[0242] This embodiment sequentially prepares the above-mentioned zirconium oxide composite powder and dental restoration according to the following steps:
[0243] B1, providing stabilized zirconia powder, colorant, dispersant, antistatic agent and binder, wherein the mass ratio of the stabilized zirconia powder, colorant, dispersant, antistatic agent and binder is 109.2:1.0:4.5:3.0:8.0, the colorant is a mixture of iron oxide, neodymium oxide and praseodymium oxide in a mass ratio of 1:0.1:0.1, the dispersant is sodium oleate, the antistatic agent is n-octanol, and the binder is carboxymethyl cellulose;
[0244] B2, diluting the above-mentioned dispersant, antistatic agent and binder with a diluent, wherein the mass ratio of the dispersant to the diluent is 1:8, the mass ratio of the antistatic agent to the diluent is 1:15, and the mass ratio of the binder to the diluent is 1:10;
[0245] B3, mixing the above materials to obtain a slurry, wherein the rotation speed of the mixing process is 45 rpm and the mixing time is 2 h;
[0246] B4, drying the slurry by a paddle dryer to obtain the zirconium oxide composite powder, wherein the initial temperature is 250° C., the end temperature is 120° C., the operating frequency of the granulation part of the drying equipment is 9000 rpm, the moisture content is controlled to 0.74%, and the granulation particle size D50 is 71 μm;
[0247] B5, the mass ratio of zirconium oxide to yttrium oxide in the zirconium oxide composite powder obtained in this embodiment is 100:9.2, the zirconium oxide composite powder obtained in Example 1 and the composite powder obtained in this embodiment are mixed in a mass ratio of 4:1, and the mixed zirconium oxide composite powder is pressed at a pressing pressure of 40 MPa to form;
[0248] B6, plastic sealing is performed using a cold isostatic pressure of 205 MPa, and the product is placed in a cold isostatic press for pressurized exhaust;
[0249] B7, bisque firing and debinding at 1010°C;
[0250] B8, engraving;
[0251] B9, finally fired at 1520℃ to form porcelain;
[0252] B10, polishing, glazing and reshaping the blank obtained in step B9 to obtain the dental restoration.
[0253] Example 10
[0254] This embodiment sequentially prepares the above-mentioned zirconium oxide composite powder and dental restoration according to the following steps:
[0255] B1, providing stabilized zirconia powder, colorant, dispersant, antistatic agent and binder, wherein the mass ratio of the stabilized zirconia powder, colorant, dispersant, antistatic agent and binder is 91:1.5:5.0:4.0:10.0, the colorant is a mixture of iron oxide, neodymium oxide and cerium oxide in a mass ratio of 1:0.1:0.1, the dispersant is sodium oleate, the antistatic agent is glycerol, and the binder is polymethyl methacrylate;
[0256] B2, diluting the above-mentioned dispersant, antistatic agent and binder with a diluent, wherein the mass ratio of the dispersant to the diluent is 1:6, the mass ratio of the antistatic agent to the diluent is 1:5, and the mass ratio of the binder to the diluent is 1:8;
[0257] B3, mixing the above materials to obtain a slurry, wherein the rotation speed of the mixing process is 55 rpm and the mixing time is 3 hours;
[0258] B4, drying the slurry by a paddle dryer to obtain the zirconium oxide composite powder, wherein the initial temperature is 250° C., the end temperature is 120° C., the operating frequency of the granulation part of the drying equipment is 10000 rpm, the moisture content is controlled to 0.64%, and the granulation particle size D50 is 62 μm;
[0259] B5, the mass ratio of zirconium oxide to yttrium oxide in the zirconium oxide composite powder obtained in this embodiment is 85:6.0, the zirconium oxide composite powder obtained in Example 1 and the composite powder obtained in this embodiment are mixed in a mass ratio of 4:1, and the mixed zirconium oxide composite powder is pressed at a pressing pressure of 60 MPa to form;
[0260] B6, plastic sealing is performed using a cold isostatic pressure of 215 MPa, and the product is placed in a cold isostatic press for pressurized exhaust;
[0261] B7, bisque firing and debinding at 1020°C;
[0262] B8, engraving;
[0263] B9, finally fired at 1540℃ to form porcelain;
[0264] B10, polishing, glazing and reshaping the blank obtained in step B9 to obtain the dental restoration.
[0265] Embodiment 11
[0266] This embodiment sequentially prepares the above-mentioned zirconium oxide composite powder and dental restoration according to the following steps:
[0267] B1, providing stabilized zirconia powder, colorant, dispersant, antistatic agent and binder, wherein the mass ratio of the stabilized zirconia powder, colorant, dispersant, antistatic agent and binder is 93.3:1.5:5.0:5.0:1.5, the colorant is a mixture of iron oxide, neodymium oxide and cobalt oxide in a mass ratio of 1:0.1:0.1, the dispersant is sodium hexametaphosphate, the antistatic agent is glycerol, and the binder is polymethyl methacrylate;
[0268] B2, diluting the above-mentioned dispersant, antistatic agent and binder with a diluent, wherein the mass ratio of the dispersant to the diluent is 1:11, the mass ratio of the antistatic agent to the diluent is 1:10, and the mass ratio of the binder to the diluent is 1:6;
[0269] B3, mixing the above materials to obtain a slurry, wherein the rotation speed of the mixing process is 65 rpm and the mixing time is 4 hours;
[0270] B4, drying the slurry by high-speed centrifugal spraying to obtain the zirconium oxide composite powder, wherein the initial temperature is 250°C, the end temperature is 120°C, the operating frequency of the granulation part of the drying equipment is 10500rpm, the moisture content is controlled to 0.55%, and the granulation particle size D50 is 54μm;
[0271] B5, the mass ratio of zirconium oxide to yttrium oxide in the zirconium oxide composite powder obtained in this embodiment is 87:6.3, the zirconium oxide composite powder obtained in Example 1 and the composite powder obtained in this embodiment are mixed in a mass ratio of 4:1, and the mixed zirconium oxide composite powder is pressed at a pressing pressure of 80 MPa to form;
[0272] B6, plastic sealing is performed using a cold isostatic pressure of 225 MPa, and the product is placed in a cold isostatic press for pressurized exhaust;
[0273] B7, bisque firing and debinding at 1040°C;
[0274] B8, engraving;
[0275] B9, finally fired at 1550℃ to form porcelain;
[0276] B10, polishing, glazing and reshaping the blank obtained in step B9 to obtain the dental restoration.
[0277] Example 12
[0278] This embodiment sequentially prepares the above-mentioned zirconium oxide composite powder and dental restoration according to the following steps:
[0279] B1, providing stabilized zirconia powder, colorant, dispersant, antistatic agent and binder, wherein the mass ratio of the stabilized zirconia powder, colorant, dispersant, antistatic agent and binder is 95.6:2.5:4.5:1.5:2.5, the colorant is a mixture of iron oxide, neodymium oxide and praseodymium oxide in a mass ratio of 1:0.1:0.1, the dispersant is sodium hexametaphosphate, the antistatic agent is glycerol, and the binder is polymethyl methacrylate;
[0280] B2, diluting the above-mentioned dispersant, antistatic agent and binder with a diluent, wherein the mass ratio of the dispersant to the diluent is 1:10, the mass ratio of the antistatic agent to the diluent is 1:15, and the mass ratio of the binder to the diluent is 1:10;
[0281] B3, mixing the above materials to obtain a slurry, wherein the rotation speed of the mixing process is 75 rpm and the mixing time is 5 h;
[0282] B4, drying the slurry by high-speed centrifugal spraying to obtain the zirconium oxide composite powder, wherein the initial temperature is 250° C., the end temperature is 120° C., the operating frequency of the granulation part of the drying equipment is 11000 rpm, the moisture content is controlled to 0.46%, and the granulation particle size D50 is 47 μm;
[0283] B5, the mass ratio of zirconium oxide to yttrium oxide in the zirconium oxide composite powder obtained in this embodiment is 89:6.6, the zirconium oxide composite powder obtained in Example 1 and the composite powder obtained in this embodiment are mixed in a mass ratio of 4:1, and the mixed zirconium oxide composite powder is pressed at a pressing pressure of 100 MPa to form;
[0284] B6, plastic sealing is performed using a cold isostatic pressure of 235 MPa, and the product is placed in a cold isostatic press for pressurized exhaust;
[0285] B7, bisque firing and debinding at 1060°C;
[0286] B8, engraving;
[0287] B9, finally fired at 1455℃ to form porcelain;
[0288] B10, polishing, glazing and reshaping the blank obtained in step B9 to obtain the dental restoration.
[0289] Embodiment 13
[0290] This embodiment sequentially prepares the above-mentioned zirconium oxide composite powder and dental restoration according to the following steps:
[0291] B1, providing stabilized zirconia powder, colorant, dispersant, antistatic agent and binder, wherein the mass ratio of the stabilized zirconia powder, colorant, dispersant, antistatic agent and binder is 97.9:2.5:4.0:2.5:3.5, the colorant is a mixture of iron oxide, neodymium oxide and cerium oxide in a mass ratio of 1:0.1:0.1, the dispersant is fatty alcohol polyethylene ether (AEO9), the antistatic agent is diethylene glycol methyl ether, and the binder is sodium alginate;
[0292] B2, diluting the above-mentioned dispersant, antistatic agent and binder with a diluent, wherein the mass ratio of the dispersant to the diluent is 1:9, the mass ratio of the antistatic agent to the diluent is 1:5, and the mass ratio of the binder to the diluent is 1:5;
[0293] B3, mixing the above materials to obtain a slurry, wherein the rotation speed of the mixing process is 85 rpm and the mixing time is 6 hours;
[0294] B4, drying the slurry by high-speed centrifugal spraying to obtain the zirconium oxide composite powder, wherein the initial temperature is 180° C., the end temperature is 120° C., the operating frequency of the granulation part of the drying equipment is 8500 rpm, the moisture content is controlled to 0.75%, and the granulation particle size D50 is 75 μm;
[0295] B5, the mass ratio of zirconium oxide to yttrium oxide in the zirconium oxide composite powder obtained in this embodiment is 91:6.9, the zirconium oxide composite powder obtained in Example 1 and the composite powder obtained in this embodiment are mixed in a mass ratio of 4:1, and the mixed zirconium oxide composite powder is pressed at a pressing pressure of 20 MPa to form;
[0296] B6, plastic sealing is performed using a cold isostatic pressure of 245 MPa, and the product is placed in a cold isostatic press for pressurized exhaust;
[0297] B7, bisque firing and debinding at 1080°C;
[0298] B8, engraving;
[0299] B9, finally fired at 1485℃ to form porcelain;
[0300] B10, polishing, glazing and reshaping the blank obtained in step B9 to obtain the dental restoration.
[0301] Embodiment 14
[0302] This embodiment sequentially prepares the above-mentioned zirconium oxide composite powder and dental restoration according to the following steps:
[0303] B1, providing stabilized zirconia powder, colorant, dispersant, antistatic agent and binder, wherein the mass ratio of the stabilized zirconia powder, colorant, dispersant, antistatic agent and binder is 100.4:5.0:3.5:3.5:4.5, the colorant is a mixture of iron oxide, cobalt oxide and praseodymium oxide in a mass ratio of 1:0.1:0.1, the dispersant is fatty alcohol polyethylene ether (AEO9), the antistatic agent is diethylene glycol methyl ether, and the binder is sodium alginate;
[0304] B2, diluting the above-mentioned dispersant, antistatic agent and binder with a diluent, wherein the mass ratio of the dispersant to the diluent is 1:11, the mass ratio of the antistatic agent to the diluent is 1:10, and the mass ratio of the binder to the diluent is 1:10;
[0305] B3, mixing the above materials to obtain a slurry, wherein the rotation speed of the mixing process is 33 rpm and the mixing time is 7 hours;
[0306] B4, drying the slurry by high-speed centrifugal spraying to obtain the zirconium oxide composite powder, wherein the initial temperature is 280°C, the end temperature is 120°C, the operating frequency of the granulation part of the drying equipment is 9000rpm, the moisture content is controlled to 0.66%, and the granulation particle size D50 is 69μm;
[0307] B5, the mass ratio of zirconium oxide to yttrium oxide in the zirconium oxide composite powder obtained in this embodiment is 93:7.4, the zirconium oxide composite powder obtained in Example 1 and the composite powder obtained in this embodiment are mixed in a mass ratio of 4:1, and the mixed zirconium oxide composite powder is pressed at a pressing pressure of 30 MPa to form;
[0308] B6, plastic sealing is performed using a cold isostatic pressure of 240 MPa, and the product is placed in a cold isostatic press for pressurized exhaust;
[0309] B7, bisque firing and debinding at 1095°C;
[0310] B8, engraving;
[0311] B9, finally fired at 1495℃ to form porcelain;
[0312] B10, polishing, glazing and reshaping the blank obtained in step B9 to obtain the dental restoration.
[0313] Embodiment 15
[0314] This embodiment sequentially prepares the above-mentioned zirconium oxide composite powder and dental restoration according to the following steps:
[0315] B1, providing stabilized zirconia powder, colorant, dispersant, antistatic agent and binder, wherein the mass ratio of the stabilized zirconia powder, colorant, dispersant, antistatic agent and binder is 102.9:5.0:3.0:4.5:5.5, the colorant is a mixture of iron oxide, praseodymium oxide and cerium oxide in a mass ratio of 1:0.1:0.1, the dispersant is fatty alcohol polyethylene ether (AEO9), the antistatic agent is diethylene glycol methyl ether, and the binder is sodium alginate;
[0316] B2, diluting the above-mentioned dispersant, antistatic agent and binder with a diluent, wherein the mass ratio of the dispersant to the diluent is 1:10, the mass ratio of the antistatic agent to the diluent is 1:15, and the mass ratio of the binder to the diluent is 1:15;
[0317] B3, mixing the above materials to obtain a slurry, wherein the rotation speed of the mixing process is 43 rpm and the mixing time is 8 hours;
[0318] B4, drying the slurry by high-speed centrifugal spraying to obtain the zirconium oxide composite powder, wherein the initial temperature is 250°C, the end temperature is 100°C, the operating frequency of the granulation part of the drying equipment is 9500rpm, the moisture content is controlled to 0.53%, and the granulation particle size D50 is 69μm;
[0319] B5, the mass ratio of zirconium oxide to yttrium oxide in the zirconium oxide composite powder obtained in this embodiment is 95:7.9, the zirconium oxide composite powder obtained in Example 1 and the composite powder obtained in this embodiment are mixed in a mass ratio of 4:1, and the mixed zirconium oxide composite powder is pressed at a pressing pressure of 40 MPa to form;
[0320] B6, plastic sealing is performed using a cold isostatic pressure of 220 MPa, and the product is placed in a cold isostatic press for pressurized exhaust;
[0321] B7, bisque firing and debinding at 1100°C;
[0322] B8, engraving;
[0323] B9, finally fired at 1525℃ to form porcelain;
[0324] B10, polishing, glazing and reshaping the blank obtained in step B9 to obtain the dental restoration.
[0325] Example 16
[0326] This embodiment sequentially prepares the above-mentioned zirconium oxide composite powder and dental restoration according to the following steps:
[0327] B1, providing stabilized zirconia powder, colorant, dispersant, antistatic agent and binder, wherein the mass ratio of the stabilized zirconia powder, colorant, dispersant, antistatic agent and binder is 105.2:8.0:2.5:5.0:6.5, the colorant is a mixture of manganese oxide, neodymium oxide and cobalt oxide in a mass ratio of 1:1:1, the dispersant is sodium tripolyphosphate, the antistatic agent is octadecylamine polyoxyethylene ether, and the binder is polyethylene oxide;
[0328] B2, diluting the above-mentioned dispersant, antistatic agent and binder with a diluent, wherein the mass ratio of the dispersant to the diluent is 1:9, the mass ratio of the antistatic agent to the diluent is 1:5, and the mass ratio of the binder to the diluent is 1:5;
[0329] B3, mixing the above materials to obtain a slurry, wherein the rotation speed of the mixing process is 53 rpm and the mixing time is 9 hours;
[0330] B4, drying the slurry by high-speed centrifugal spraying to obtain the zirconium oxide composite powder, wherein the initial temperature is 250°C, the end temperature is 150°C, the operating frequency of the granulation part of the drying equipment is 10500rpm, the moisture content is controlled to 0.42%, and the granulation particle size D50 is 54μm;
[0331] B5, the mass ratio of zirconium oxide to yttrium oxide in the zirconium oxide composite powder obtained in this embodiment is 97:8.2, the zirconium oxide composite powder obtained in Example 1 and the composite powder mixed in this embodiment are mixed in a mass ratio of 4:1, and the obtained zirconium oxide composite powder is pressed at a pressing pressure of 60 MPa to form;
[0332] B6, plastic sealing is performed using a cold isostatic pressure of 200 MPa, and the product is placed in a cold isostatic press for pressurized exhaust;
[0333] B7, bisque firing and debinding at 1105°C;
[0334] B8, engraving;
[0335] B9, finally fired at 1535℃ to form porcelain;
[0336] B10, polishing, glazing and reshaping the blank obtained in step B9 to obtain the dental restoration.
[0337] Embodiment 17
[0338] This embodiment sequentially prepares the above-mentioned zirconium oxide composite powder and dental restoration according to the following steps:
[0339] B1, providing stabilized zirconia powder, colorant, dispersant, antistatic agent and binder, wherein the mass ratio of the stabilized zirconia powder, colorant, dispersant, antistatic agent and binder is 107.5:8.0:2.0:2.5:7.5, the colorant is a mixture of neodymium oxide, cobalt oxide and praseodymium oxide in a mass ratio of 1:1:1, the dispersant is sodium tripolyphosphate, the antistatic agent is octadecylamine polyoxyethylene ether, and the binder is polyethylene oxide;
[0340] B2, diluting the above-mentioned dispersant, antistatic agent and binder with a diluent, wherein the mass ratio of the dispersant to the diluent is 1:8, the mass ratio of the antistatic agent to the diluent is 1:10, and the mass ratio of the binder to the diluent is 1:10;
[0341] B3, mixing the above materials to obtain a slurry, wherein the rotation speed of the mixing process is 63 rpm and the mixing time is 10 h;
[0342] B4, drying the slurry by high-speed centrifugal spraying to obtain the zirconium oxide composite powder, wherein the initial temperature is 250° C., the end temperature is 120° C., the operating frequency of the granulation part of the drying equipment is 11500 rpm, the moisture content is controlled to 0.32%, and the granulation particle size D50 is 48 μm;
[0343] B5, the mass ratio of zirconium oxide to yttrium oxide in the zirconium oxide composite powder obtained in this embodiment is 99:8.5, the zirconium oxide composite powder obtained in Example 1 and the composite powder obtained in this embodiment are mixed in a mass ratio of 4:1, and the mixed zirconium oxide composite powder is pressed at a pressing pressure of 80 MPa to form;
[0344] B6, plastic sealing is performed using a cold isostatic pressure of 190 MPa, and the product is placed in a cold isostatic press for pressurized exhaust;
[0345] B7, bisque firing and debinding at 1115°C;
[0346] B8, engraving;
[0347] B9, finally fired at 1545℃ to form porcelain;
[0348] B10, polishing, glazing and reshaping the blank obtained in step B9 to obtain the dental restoration.
[0349] Embodiment 18
[0350] This embodiment sequentially prepares the above-mentioned zirconium oxide composite powder and dental restoration according to the following steps:
[0351] B1, providing stabilized zirconia powder, colorant, dispersant, antistatic agent and binder, wherein the mass ratio of the stabilized zirconia powder, colorant, dispersant, antistatic agent and binder is 109.2:10.0:1.5:3.5:10.0, the colorant is a mixture of cobalt oxide, praseodymium oxide and cerium oxide in a mass ratio of 1:1:1, the dispersant is sodium tripolyphosphate, the antistatic agent is octadecylamine polyoxyethylene ether, and the binder is polyethylene oxide;
[0352] B2, diluting the above-mentioned dispersant, antistatic agent and binder with a diluent, wherein the mass ratio of the dispersant to the diluent is 1:12, the mass ratio of the antistatic agent to the diluent is 1:15, and the mass ratio of the binder to the diluent is 1:15;
[0353] B3, mixing the above materials to obtain a slurry, wherein the rotation speed of the mixing process is 83 rpm and the mixing time is 4 hours;
[0354] B4, drying the slurry by high-speed centrifugal spraying to obtain the zirconium oxide composite powder, wherein the initial temperature is 250° C., the end temperature is 120° C., the operating frequency of the granulation part of the drying equipment is 15000 rpm, the moisture content is controlled to 0.08%, and the granulation particle size D50 is 37 μm;
[0355] B5, the mass ratio of zirconium oxide to yttrium oxide in the zirconium oxide composite powder obtained in this embodiment is 100:9.2, the zirconium oxide composite powder obtained in Example 1 and the composite powder obtained in this embodiment are mixed in a mass ratio of 4:1, and the mixed zirconium oxide composite powder is pressed at a pressing pressure of 100 MPa to form;
[0356] B6, plastic sealing is performed using a cold isostatic pressure of 180 MPa, and the product is placed in a cold isostatic press for pressurized exhaust;
[0357] B7, bisque firing and debinding at 1200°C;
[0358] B8, engraving;
[0359] B9, finally fired at 1550℃ to form porcelain;
[0360] B10, polishing, glazing and reshaping the blank obtained in step B9 to obtain the dental restoration.
[0361] Comparative Example 1
[0362] This embodiment sequentially prepares the above-mentioned zirconium oxide composite powder and dental restoration according to the following steps:
[0363] B1, providing stabilized zirconia powder, colorant, dispersant, antistatic agent and binder, wherein the mass ratio of the stabilized zirconia powder, colorant, dispersant, antistatic agent and binder is 86:4.0:0.1:0.2:0.2, the colorant is iron oxide, the dispersant is sodium polymethacrylate, the antistatic agent is polyethylene glycol, and the binder is polyvinyl alcohol;
[0364] B2, diluting the above-mentioned dispersant, antistatic agent and binder with a diluent, wherein the mass ratio of the dispersant to the diluent is 1:2, the mass ratio of the antistatic agent to the diluent is 1:3, and the mass ratio of the binder to the diluent is 1:2;
[0365] B3, mixing the above materials to obtain a slurry, wherein the rotation speed of the mixing process is 20 rpm and the mixing time is 1 h;
[0366] B4, drying the slurry by high-speed centrifugal spraying to obtain the zirconium oxide composite powder, wherein the initial temperature is 175°C, the end temperature is 155°C, the operating frequency of the granulation part of the drying equipment is 16000rpm, the moisture content is controlled to 0.15%, and the granulation particle size D50 is 33μm;
[0367] B5, the mass ratio of zirconium oxide to yttrium oxide in the zirconium oxide composite powder obtained in this embodiment is 80:6.0, the zirconium oxide composite powder obtained in Example 1 and the composite powder obtained in this embodiment are mixed in a mass ratio of 4:1, and the mixed zirconium oxide composite powder is pressed at a pressing pressure of 120 MPa to form;
[0368] B6, plastic sealing is performed using a cold isostatic pressure of 160 MPa, and the product is placed in a cold isostatic press for pressurized exhaust;
[0369] B7, bisque firing and debinding at 1150°C;
[0370] B8, engraving;
[0371] B9, finally fired at 1450℃ to form porcelain;
[0372] B10, polishing, glazing and reshaping the blank obtained in step B9 to obtain the dental restoration.
[0373] Comparative Example 2
[0374] This embodiment sequentially prepares the above-mentioned zirconium oxide composite powder and dental restoration according to the following steps:
[0375] B1, providing stabilized zirconia powder, colorant, dispersant, antistatic agent and binder, wherein the mass ratio of the stabilized zirconia powder, colorant, dispersant, antistatic agent and binder is 89:6.0:0.2:0.4:0.4, the colorant is a mixture of iron oxide and manganese oxide in a mass ratio of 1:2, the dispersant is sodium polymethacrylate, the antistatic agent is polyethylene glycol, and the binder is polyvinyl alcohol;
[0376] B2, diluting the above-mentioned dispersant, antistatic agent and binder with a diluent, wherein the mass ratio of the dispersant to the diluent is 1:4, the mass ratio of the antistatic agent to the diluent is 1:4, and the mass ratio of the binder to the diluent is 1:3;
[0377] B3, mixing the above materials to obtain a slurry, wherein the rotation speed of the mixing process is 40 rpm and the mixing time is 3 h;
[0378] B4, drying the slurry by high-speed centrifugal spraying to obtain the zirconium oxide composite powder, wherein the initial temperature is 270°C, the end temperature is 150°C, the operating frequency of the granulation part of the drying equipment is 16000rpm, the moisture content is controlled to 0.20%, and the granulation particle size D50 is 38μm;
[0379] B5, the mass ratio of zirconium oxide to yttrium oxide in the zirconium oxide composite powder obtained in this embodiment is 82:7.0, the zirconium oxide composite powder obtained in Example 1 and the composite powder obtained in this embodiment are mixed in a mass ratio of 4:1, and the mixed zirconium oxide composite powder is pressed at a pressing pressure of 60 MPa to form;
[0380] B6, plastic sealing is performed using a cold isostatic pressure of 170 MPa, and the product is placed in a cold isostatic press for pressurized exhaust;
[0381] B7, bisque firing and debinding at 1000°C;
[0382] B8, engraving;
[0383] B9, finally fired at 1560℃ to form porcelain;
[0384] B10, polishing, glazing and reshaping the blank obtained in step B9 to obtain the dental restoration.
[0385] Comparative Example 3
[0386] This embodiment sequentially prepares the above-mentioned zirconium oxide composite powder and dental restoration according to the following steps:
[0387] B1, providing stabilized zirconia powder, colorant, dispersant, antistatic agent and binder, wherein the mass ratio of the stabilized zirconia powder, colorant, dispersant, antistatic agent and binder is 92:8.0:0.3:0.6:0.6, the colorant is a mixture of iron oxide and neodymium oxide in a mass ratio of 1:1.5, the dispersant is sodium dodecylbenzene sulfonate, the antistatic agent is polyethyleneimine, and the binder is epoxy resin;
[0388] B2, diluting the above-mentioned dispersant, antistatic agent and binder with a diluent, wherein the mass ratio of the dispersant to the diluent is 1:6, the mass ratio of the antistatic agent to the diluent is 1:5, and the mass ratio of the binder to the diluent is 1:4;
[0389] B3, mixing the above materials to obtain a slurry, wherein the rotation speed of the mixing process is 60 rpm and the mixing time is 5 hours;
[0390] B4, drying the slurry by high-speed centrifugal spraying to obtain the zirconium oxide composite powder, wherein the initial temperature is 170° C., the end temperature is 90° C., the operating frequency of the granulation part of the drying equipment is 16000 rpm, the moisture content is controlled to 0.28%, and the granulation particle size D50 is 35 μm;
[0391] B5, the mass ratio of zirconium oxide to yttrium oxide in the zirconium oxide composite powder obtained in this embodiment is 84:8.0, the zirconium oxide composite powder obtained in Example 1 and the composite powder obtained in this embodiment are mixed in a mass ratio of 4:1, and the mixed zirconium oxide composite powder is pressed at a pressing pressure of 30 MPa to form;
[0392] B6, plastic sealing is performed using a cold isostatic pressure of 180 MPa, and the product is placed in a cold isostatic press for pressurized exhaust;
[0393] B7, bisque firing and debinding at 1030°C;
[0394] B8, engraving;
[0395] B9, finally fired at 1400℃ to form porcelain;
[0396] B10, polishing, glazing and reshaping the blank obtained in step B9 to obtain the dental restoration.
[0397] Comparative Example 4
[0398] This embodiment sequentially prepares the above-mentioned zirconium oxide composite powder and dental restoration according to the following steps:
[0399] B1, providing stabilized zirconia powder, colorant, dispersant, antistatic agent and binder, wherein the mass ratio of the stabilized zirconia powder, colorant, dispersant, antistatic agent and binder is 112:10.0:0.4:0.8:0.8, the colorant is iron oxide, the dispersant is sodium dodecylbenzene sulfonate, the antistatic agent is polystyrene imine, and the binder is epoxy resin;
[0400] B2, diluting the above-mentioned dispersant, antistatic agent and binder with a diluent, wherein the mass ratio of the dispersant to the diluent is 1:8, the mass ratio of the antistatic agent to the diluent is 1:3, and the mass ratio of the binder to the diluent is 1:1;
[0401] B3, mixing the above materials to obtain a slurry, wherein the rotation speed of the mixing process is 100 rpm and the mixing time is 7 hours;
[0402] B4, drying the slurry by high-speed centrifugal spraying to obtain the zirconium oxide composite powder, wherein the initial temperature is 290° C., the end temperature is 160° C., the operating frequency of the granulation part of the drying equipment is 4500 rpm, the moisture content is controlled to 1.21%, and the granulation particle size D50 is 105 μm;
[0403] B5, the mass ratio of zirconium oxide to yttrium oxide in the zirconium oxide composite powder obtained in this embodiment is 103:9.0, the zirconium oxide composite powder obtained in Example 1 and the composite powder obtained in this embodiment are mixed in a mass ratio of 4:1, and the mixed zirconium oxide composite powder is pressed at a pressing pressure of 15 MPa to form;
[0404] B6, plastic sealing is performed using a cold isostatic pressure of 250 MPa, and the product is placed in a cold isostatic press for pressurized exhaust;
[0405] B7, bisque firing and debinding at 1050°C;
[0406] B8, engraving;
[0407] B9, finally fired at 1420℃ to form porcelain;
[0408] B10, polishing, glazing and reshaping the blank obtained in step B9 to obtain the dental restoration.
[0409] Comparative Example 5
[0410] This embodiment sequentially prepares the above-mentioned zirconium oxide composite powder and dental restoration according to the following steps:
[0411] B1, providing stabilized zirconia powder, colorant, dispersant, antistatic agent and binder, wherein the mass ratio of the stabilized zirconia powder, colorant, dispersant, antistatic agent and binder is 115:12.0:0.1:0.2:1.0, the colorant is a mixture of iron oxide and praseodymium oxide in a mass ratio of 1:2, the dispersant is sodium polymethacrylate, the antistatic agent is polyethylene glycol, and the binder is polyvinyl alcohol;
[0412] B2, diluting the above-mentioned dispersant, antistatic agent and binder with a diluent, wherein the mass ratio of the dispersant to the diluent is 1:2, the mass ratio of the antistatic agent to the diluent is 1:4, and the mass ratio of the binder to the diluent is 1:2;
[0413] B3, mixing the above materials to obtain a slurry, wherein the rotation speed of the mixing process is 20 rpm and the mixing time is 11 h;
[0414] B4, drying the slurry by high-speed centrifugal spraying to obtain the zirconium oxide composite powder, wherein the initial temperature is 160° C., the end temperature is 150° C., the operating frequency of the granulation part of the drying equipment is 4500 rpm, the moisture content is controlled to 1.07%, and the granulation particle size D50 is 110 μm;
[0415] B5, the mass ratio of zirconium oxide to yttrium oxide in the zirconium oxide composite powder obtained in this embodiment is 106:9.0, the zirconium oxide composite powder obtained in Example 1 and the composite powder obtained in this embodiment are mixed in a mass ratio of 4:1, and the mixed zirconium oxide composite powder is pressed at a pressing pressure of 120 MPa to form;
[0416] B6, plastic sealing is performed using a cold isostatic pressure of 260 MPa, and the product is placed in a cold isostatic press for pressurized exhaust;
[0417] B7, bisque firing and debinding at 1070°C;
[0418] B8, engraving;
[0419] B9, finally fired at 1450℃ to form porcelain;
[0420] B10, polishing, glazing and reshaping the blank obtained in step B9 to obtain the dental restoration.
[0421] Comparative Example 6
[0422] This embodiment sequentially prepares the above-mentioned zirconium oxide composite powder and dental restoration according to the following steps:
[0423] B1, providing stabilized zirconia powder, colorant, dispersant, antistatic agent and binder, wherein the mass ratio of the stabilized zirconia powder, colorant, dispersant, antistatic agent and binder is 119.5:4.0:0.2:0.4:0.2, the colorant is a mixture of iron oxide and cerium oxide in a mass ratio of 1:1.5, the dispersant is sodium polymethacrylate, the antistatic agent is polyethylene glycol, and the binder is polyvinyl alcohol;
[0424] B2, diluting the above-mentioned dispersant, antistatic agent and binder with a diluent, wherein the mass ratio of the dispersant to the diluent is 1:4, the mass ratio of the antistatic agent to the diluent is 1:5, and the mass ratio of the binder to the diluent is 1:3;
[0425] B3, mixing the above materials to obtain a slurry, wherein the rotation speed of the mixing process is 40 rpm and the mixing time is 1 hour;
[0426] B4, drying the slurry by high-speed centrifugal spraying to obtain the zirconium oxide composite powder, wherein the initial temperature is 270°C, the end temperature is 90°C, the operating frequency of the granulation part of the drying equipment is 4500rpm, the moisture content is controlled to 1.19%, and the granulation particle size D50 is 117μm;
[0427] B5, the mass ratio of zirconium oxide to yttrium oxide in the zirconium oxide composite powder obtained in this embodiment is 110:9.5, the zirconium oxide composite powder obtained in Example 1 and the composite powder obtained in this embodiment are mixed in a mass ratio of 4:1, and the mixed zirconium oxide composite powder is pressed at a pressing pressure of 60 MPa to form;
[0428] B6, plastic sealing is performed using a cold isostatic pressure of 160 MPa, and the product is placed in a cold isostatic press for pressurized exhaust;
[0429] B7, bisque firing and debinding at 1090°C;
[0430] B8, engraving;
[0431] B9, finally fired at 1560℃ to form porcelain;
[0432] B10, polishing, glazing and reshaping the blank obtained in step B9 to obtain the dental restoration.
[0433] Comparative Example 7
[0434] This embodiment sequentially prepares the above-mentioned zirconium oxide composite powder and dental restoration according to the following steps:
[0435] B1, providing stabilized zirconia powder, colorant, dispersant, antistatic agent and binder, wherein the mass ratio of the stabilized zirconia powder, colorant, dispersant, antistatic agent and binder is 80:6.0:6.0:0.3:0.6:0.4, the colorant is a mixture of iron oxide, neodymium oxide and manganese oxide in a mass ratio of 1:0.5:1.5, the dispersant is sodium polymethacrylate, the antistatic agent is polyethylene glycol, and the binder is polyvinyl alcohol;
[0436] B2, diluting the above-mentioned dispersant, antistatic agent and binder with a diluent, wherein the mass ratio of the dispersant to the diluent is 1:2, the mass ratio of the antistatic agent to the diluent is 1:3, and the mass ratio of the binder to the diluent is 1:4;
[0437] B3, mixing the above materials to obtain a slurry, wherein the rotation speed of the mixing process is 60 rpm and the mixing time is 3 h;
[0438] B4, drying the slurry by high-speed centrifugal spraying to obtain the zirconium oxide composite powder, wherein the initial temperature is 170°C, the end temperature is 160°C, the operating frequency of the granulation part of the drying equipment is 16000rpm, the moisture content is controlled to 0.18%, and the granulation particle size D50 is 42μm;
[0439] B5, the mass ratio of zirconium oxide to yttrium oxide in the zirconium oxide composite powder obtained in this embodiment is 80:6.0, the zirconium oxide composite powder obtained in Example 1 and the composite powder obtained in this embodiment are mixed in a mass ratio of 4:1, and the mixed zirconium oxide composite powder is pressed at a pressing pressure of 30 MPa to form;
[0440] B6, plastic sealing is performed using a cold isostatic pressure of 170 MPa, and the product is placed in a cold isostatic press for pressurized exhaust;
[0441] B7, bisque firing and debinding at 1110°C;
[0442] B8, engraving;
[0443] B9, finally fired at 1400℃ to form porcelain;
[0444] B10, polishing, glazing and reshaping the blank obtained in step B9 to obtain the dental restoration.
[0445] Comparative Example 8
[0446] This embodiment sequentially prepares the above-mentioned zirconium oxide composite powder and dental restoration according to the following steps:
[0447] B1, providing stabilized zirconia powder, colorant, dispersant, antistatic agent and binder, wherein the mass ratio of the stabilized zirconia powder, colorant, dispersant, antistatic agent and binder is 89:8.0:0.4:0.8:0.6, the colorant is a mixture of iron oxide, neodymium oxide and cobalt oxide in a mass ratio of 1:1.5:0.5, the dispersant is sodium polymethacrylate, the antistatic agent is polyethylene glycol, and the binder is polyvinyl alcohol;
[0448] B2, diluting the above-mentioned dispersant, antistatic agent and binder with a diluent, wherein the mass ratio of the dispersant to the diluent is 1:4, the mass ratio of the antistatic agent to the diluent is 1:4, and the mass ratio of the binder to the diluent is 1:1;
[0449] B3, mixing the above materials to obtain a slurry, wherein the rotation speed of the mixing process is 100 rpm and the mixing time is 5 hours;
[0450] B4, drying the slurry by high-speed centrifugal spraying to obtain the zirconium oxide composite powder, wherein the initial temperature is 290° C., the end temperature is 150° C., the operating frequency of the granulation part of the drying equipment is 16000 rpm, the moisture content is controlled to 0.21%, and the granulation particle size D50 is 39 μm;
[0451] B5, the mass ratio of zirconium oxide to yttrium oxide in the zirconium oxide composite powder obtained in this embodiment is 82:7.0, the zirconium oxide composite powder obtained in Example 1 and the composite powder obtained in this embodiment are mixed in a mass ratio of 4:1, and the mixed zirconium oxide composite powder is pressed at a pressing pressure of 15 MPa to form;
[0452] B6, plastic sealing is performed using a cold isostatic pressure of 180 MPa, and the product is placed in a cold isostatic press for pressurized exhaust;
[0453] B7, bisque firing and debinding at 900°C;
[0454] B8, engraving;
[0455] B9, finally fired at 1420℃ to form porcelain;
[0456] B10, polishing, glazing and reshaping the blank obtained in step B9 to obtain the dental restoration.
[0457] Comparative Example 9
[0458] This embodiment sequentially prepares the above-mentioned zirconium oxide composite powder and dental restoration according to the following steps:
[0459] B1, providing stabilized zirconia powder, colorant, dispersant, antistatic agent and binder, wherein the mass ratio of the stabilized zirconia powder, colorant, dispersant, antistatic agent and binder is 92:10.0:0.2:0.2:0.8, the colorant is a mixture of iron oxide, neodymium oxide and praseodymium oxide in a mass ratio of 1:0.1:1.2, the dispersant is sodium dodecyl sulfate, the antistatic agent is silicone oil, and the binder is polyurethane;
[0460] B2, diluting the above-mentioned dispersant, antistatic agent and binder with a diluent, wherein the mass ratio of the dispersant to the diluent is 1:6, the mass ratio of the antistatic agent to the diluent is 1:5, and the mass ratio of the binder to the diluent is 1:2;
[0461] B3, mixing the above materials to obtain a slurry, wherein the rotation speed of the mixing process is 20 rpm and the mixing time is 7 hours;
[0462] B4, drying the slurry by high-speed centrifugal spraying to obtain the zirconium oxide composite powder, wherein the initial temperature is 160° C., the end temperature is 90° C., the operating frequency of the granulation part of the drying equipment is 16000 rpm, the moisture content is controlled to 0.23%, and the granulation particle size D50 is 44 μm;
[0463] B5, the mass ratio of zirconium oxide to yttrium oxide in the zirconium oxide composite powder obtained in this embodiment is 84:8.0, the zirconium oxide composite powder obtained in Example 1 and the composite powder obtained in this embodiment are mixed in a mass ratio of 4:1, and the mixed zirconium oxide composite powder is pressed at a pressing pressure of 120 MPa to form;
[0464] B6, plastic sealing is performed using a cold isostatic pressure of 250 MPa, and the product is placed in a cold isostatic press for pressurized exhaust;
[0465] B7, bisque firing and debinding at 1010°C;
[0466] B8, engraving;
[0467] B9, finally fired at 1450℃ to form porcelain;
[0468] B10, polishing, glazing and reshaping the blank obtained in step B9 to obtain the dental restoration.
[0469] Comparative Example 10
[0470] This embodiment sequentially prepares the above-mentioned zirconium oxide composite powder and dental restoration according to the following steps:
[0471] B1, providing stabilized zirconia powder, colorant, dispersant, antistatic agent and binder, wherein the mass ratio of the stabilized zirconia powder, colorant, dispersant, antistatic agent and binder is 112:12.0:0.3:0.4:1.0, the colorant is a mixture of iron oxide, neodymium oxide and cerium oxide in a mass ratio of 1:1.2:0.1, the dispersant is sodium dodecyl sulfate, the antistatic agent is methyl silicone oil, and the binder is phenolic resin;
[0472] B2, diluting the above-mentioned dispersant, antistatic agent and binder with a diluent, wherein the mass ratio of the dispersant to the diluent is 1:8, the mass ratio of the antistatic agent to the diluent is 1:3, and the mass ratio of the binder to the diluent is 1:3;
[0473] B3, mixing the above materials to obtain a slurry, wherein the rotation speed of the mixing process is 40 rpm and the mixing time is 11 h;
[0474] B4, drying the slurry by high-speed centrifugal spraying to obtain the zirconium oxide composite powder, wherein the initial temperature is 270°C, the end temperature is 160°C, the operating frequency of the granulation part of the drying equipment is 4500rpm, the moisture content is controlled to 1.21%, and the granulation particle size D50 is 109μm;
[0475] B5, the mass ratio of zirconium oxide to yttrium oxide in the zirconium oxide composite powder obtained in this embodiment is 103:9.0, the zirconium oxide composite powder obtained in Example 1 and the composite powder obtained in this embodiment are mixed in a mass ratio of 4:1, and the mixed zirconium oxide composite powder is pressed at a pressing pressure of 60 MPa to form;
[0476] B6, plastic sealing is performed using a cold isostatic pressure of 260 MPa, and the product is placed in a cold isostatic press for pressurized exhaust;
[0477] B7, bisque firing and debinding at 1020°C;
[0478] B8, engraving;
[0479] B9, finally fired at 1560℃ to form porcelain;
[0480] B10, polishing, glazing and reshaping the blank obtained in step B9 to obtain the dental restoration.
[0481] Comparative Example 11
[0482] This embodiment sequentially prepares the above-mentioned zirconium oxide composite powder and dental restoration according to the following steps:
[0483] B1, providing stabilized zirconia powder, colorant, dispersant, antistatic agent and binder, wherein the mass ratio of the stabilized zirconia powder, colorant, dispersant, antistatic agent and binder is 115:4.0:0.4:0.6:0.2, the colorant is a mixture of iron oxide, neodymium oxide and cobalt oxide in a mass ratio of 1:0.5:1.5, the dispersant is sodium dodecyl sulfate, the antistatic agent is methyl silicone oil, and the binder is phenolic resin;
[0484] B2, diluting the above-mentioned dispersant, antistatic agent and binder with a diluent, wherein the mass ratio of the dispersant to the diluent is 1:2, the mass ratio of the antistatic agent to the diluent is 1:4, and the mass ratio of the binder to the diluent is 1:4;
[0485] B3, mixing the above materials to obtain a slurry, wherein the rotation speed of the mixing process is 60 rpm and the mixing time is 1 hour;
[0486] B4, drying the slurry by high-speed centrifugal spraying to obtain the zirconium oxide composite powder, wherein the initial temperature is 170°C, the end temperature is 150°C, the operating frequency of the granulation part of the drying equipment is 4500rpm, the moisture content is controlled to 1.25%, and the granulation particle size D50 is 101μm;
[0487] B5, the mass ratio of zirconium oxide to yttrium oxide in the zirconium oxide composite powder obtained in this embodiment is 106:9.0, the zirconium oxide composite powder obtained in Example 1 and the composite powder obtained in this embodiment are mixed in a mass ratio of 4:1, and the mixed zirconium oxide composite powder is pressed at a pressing pressure of 30 MPa to form;
[0488] B6, plastic sealing is performed using a cold isostatic pressure of 160 MPa, and the product is placed in a cold isostatic press for pressurized exhaust;
[0489] B7, bisque firing and debinding at 1040°C;
[0490] B8, engraving;
[0491] B9, finally fired at 1400℃ to form porcelain;
[0492] B10, polishing, glazing and reshaping the blank obtained in step B9 to obtain the dental restoration.
[0493] Comparative Example 12
[0494] This embodiment sequentially prepares the above-mentioned zirconium oxide composite powder and dental restoration according to the following steps:
[0495] B1, providing stabilized zirconia powder, colorant, dispersant, antistatic agent and binder, wherein the mass ratio of the stabilized zirconia powder, colorant, dispersant, antistatic agent and binder is 119.5:6.0:5.0:0.8:0.4, the colorant is a mixture of iron oxide, neodymium oxide and praseodymium oxide in a mass ratio of 1:1.5:0.5, the dispersant is sodium dodecyl sulfate, the antistatic agent is methyl silicone oil, and the binder is phenolic resin;
[0496] B2, diluting the above-mentioned dispersant, antistatic agent and binder with a diluent, wherein the mass ratio of the dispersant to the diluent is 1:4, the mass ratio of the antistatic agent to the diluent is 1:5, and the mass ratio of the binder to the diluent is 1:1;
[0497] B3, mixing the above materials to obtain a slurry, wherein the rotation speed of the mixing process is 100 rpm and the mixing time is 3 hours;
[0498] B4, drying the slurry by high-speed centrifugal spraying to obtain the zirconium oxide composite powder, wherein the initial temperature is 290° C., the end temperature is 90° C., the operating frequency of the granulation part of the drying equipment is 4500 rpm, the moisture content is controlled to 1.29%, and the granulation particle size D50 is 121 μm;
[0499] B5, the mass ratio of zirconium oxide to yttrium oxide in the zirconium oxide composite powder obtained in this embodiment is 110:9.5, the zirconium oxide composite powder obtained in Example 1 and the composite powder obtained in this embodiment are mixed in a mass ratio of 4:1, and the mixed zirconium oxide composite powder is pressed at a pressing pressure of 15 MPa to form;
[0500] B6, plastic sealing is performed using a cold isostatic pressure of 170 MPa, and the product is placed in a cold isostatic press for pressurized exhaust;
[0501] B7, bisque firing and debinding at 1060°C;
[0502] B8, engraving;
[0503] B9, finally fired at 1420℃ to form porcelain;
[0504] B10, polishing, glazing and reshaping the blank obtained in step B9 to obtain the dental restoration.
[0505] Comparative Example 13
[0506] This embodiment sequentially prepares the above-mentioned zirconium oxide composite powder and dental restoration according to the following steps:
[0507] B1, providing stabilized zirconia powder, colorant, dispersant, antistatic agent and binder, wherein the mass ratio of the stabilized zirconia powder, colorant, dispersant, antistatic agent and binder is 86:8.0:6.0:0.2:0.6, the colorant is a mixture of iron oxide, neodymium oxide and cerium oxide in a mass ratio of 1:0.1:1.2, the dispersant is sodium dodecyl sulfate, the antistatic agent is silicone oil, and the binder is polyurethane;
[0508] B2, diluting the above-mentioned dispersant, antistatic agent and binder with a diluent, wherein the mass ratio of the dispersant to the diluent is 1:2, the mass ratio of the antistatic agent to the diluent is 1:3, and the mass ratio of the binder to the diluent is 1:2;
[0509] B3, mixing the above materials to obtain a slurry, wherein the rotation speed of the mixing process is 20 rpm and the mixing time is 5 hours;
[0510] B4, drying the slurry by high-speed centrifugal spraying to obtain the zirconium oxide composite powder, wherein the initial temperature is 160°C, the end temperature is 100°C, the operating frequency of the granulation part of the drying equipment is 15500rpm, the moisture content is controlled to 0.2%, and the granulation particle size D50 is 47μm;
[0511] B5, the mass ratio of zirconium oxide to yttrium oxide in the zirconium oxide composite powder obtained in this embodiment is 80:6.0, the zirconium oxide composite powder obtained in Example 1 and the composite powder obtained in this embodiment are mixed in a mass ratio of 4:1, and the mixed zirconium oxide composite powder is pressed at a pressing pressure of 120 MPa to form;
[0512] B6, plastic sealing is performed using a cold isostatic pressure of 180 MPa, and the product is placed in a cold isostatic press for pressurized exhaust;
[0513] B7, bisque firing and debinding at 1080°C;
[0514] B8, engraving;
[0515] B9, finally fired at 1450℃ to form porcelain;
[0516] B10, polishing, glazing and reshaping the blank obtained in step B9 to obtain the dental restoration.
[0517] Comparative Example 14
[0518] This embodiment sequentially prepares the above-mentioned zirconium oxide composite powder and dental restoration according to the following steps:
[0519] B1, providing stabilized zirconia powder, colorant, dispersant, antistatic agent and binder, wherein the mass ratio of the stabilized zirconia powder, colorant, dispersant, antistatic agent and binder is 89:10.0:7.0:0.4:0.8, the colorant is a mixture of iron oxide, cobalt oxide and praseodymium oxide in a mass ratio of 1:1.2:0.1, the dispersant is sodium dodecyl sulfate, the antistatic agent is silicone oil, and the binder is polyurethane;
[0520] B2, diluting the above-mentioned dispersant, antistatic agent and binder with a diluent, wherein the mass ratio of the dispersant to the diluent is 1:4, the mass ratio of the antistatic agent to the diluent is 1:4, and the mass ratio of the binder to the diluent is 1:3;
[0521] B3, mixing the above materials to obtain a slurry, wherein the rotation speed of the mixing process is 40 rpm and the mixing time is 7 hours;
[0522] B4, drying the slurry by high-speed centrifugal spraying to obtain the zirconium oxide composite powder, wherein the initial temperature is 270°C, the end temperature is 150°C, the operating frequency of the granulation part of the drying equipment is 15500rpm, the moisture content is controlled to 0.22%, and the granulation particle size D50 is 43μm;
[0523] B5, the mass ratio of zirconium oxide to yttrium oxide in the zirconium oxide composite powder obtained in this embodiment is 82:7.0, the zirconium oxide composite powder obtained in Example 1 and the composite powder obtained in this embodiment are mixed in a mass ratio of 4:1, and the mixed zirconium oxide composite powder is pressed at a pressing pressure of 60 MPa to form;
[0524] B6, plastic sealing is performed using a cold isostatic pressure of 250 MPa, and the product is placed in a cold isostatic press for pressurized exhaust;
[0525] B7, bisque firing and debinding at 1095°C;
[0526] B8, engraving;
[0527] B9, finally fired at 1560℃ to form porcelain;
[0528] B10, polishing, glazing and reshaping the blank obtained in step B9 to obtain the dental restoration.
[0529] Comparative Example 15
[0530] This embodiment sequentially prepares the above-mentioned zirconium oxide composite powder and dental restoration according to the following steps:
[0531] B1, providing stabilized zirconia powder, colorant, dispersant, antistatic agent and binder, wherein the mass ratio of the stabilized zirconia powder, colorant, dispersant, antistatic agent and binder is 92:12.0:0.1:0.6:0.4, the colorant is a mixture of iron oxide, praseodymium oxide and cerium oxide in a mass ratio of 1:0.5:1.5, the dispersant is sodium dodecyl sulfate, the antistatic agent is silicone oil, and the binder is polyurethane;
[0532] B2, diluting the above-mentioned dispersant, antistatic agent and binder with a diluent, wherein the mass ratio of the dispersant to the diluent is 1:6, the mass ratio of the antistatic agent to the diluent is 1:5, and the mass ratio of the binder to the diluent is 1:4;
[0533] B3, mixing the above materials to obtain a slurry, wherein the rotation speed of the mixing process is 60 rpm and the mixing time is 11 hours;
[0534] B4, drying the slurry by high-speed centrifugal spraying to obtain the zirconium oxide composite powder, wherein the initial temperature is 170° C., the end temperature is 90° C., the operating frequency of the granulation part of the drying equipment is 15500 rpm, the moisture content is controlled to 0.26%, and the granulation particle size D50 is 40 μm;
[0535] B5, the mass ratio of zirconium oxide to yttrium oxide in the zirconium oxide composite powder obtained in this embodiment is 84:8.0, the zirconium oxide composite powder obtained in Example 1 and the composite powder obtained in this embodiment are mixed in a mass ratio of 4:1, and the mixed zirconium oxide composite powder is pressed at a pressing pressure of 30 MPa to form;
[0536] B6, plastic sealing is performed using a cold isostatic pressure of 260 MPa, and the product is placed in a cold isostatic press for pressurized exhaust;
[0537] B7, bisque firing and debinding at 1100°C;
[0538] B8, engraving;
[0539] B9, finally fired at 1400℃ to form porcelain;
[0540] B10, polishing, glazing and reshaping the blank obtained in step B9 to obtain the dental restoration.
[0541] Comparative Example 16
[0542] This embodiment sequentially prepares the above-mentioned zirconium oxide composite powder and dental restoration according to the following steps:
[0543] B1, providing stabilized zirconia powder, colorant, dispersant, antistatic agent and binder, wherein the mass ratio of the stabilized zirconia powder, colorant, dispersant, antistatic agent and binder is 112:12.0:0.2:0.8:0.6, the colorant is a mixture of manganese oxide, neodymium oxide and cobalt oxide in a mass ratio of 1:1.5:0.5, the dispersant is sodium dodecyl sulfate, the antistatic agent is methyl silicone oil, and the binder is phenolic resin;
[0544] B2, diluting the above-mentioned dispersant, antistatic agent and binder with a diluent, wherein the mass ratio of the dispersant to the diluent is 1:8, the mass ratio of the antistatic agent to the diluent is 1:3, and the mass ratio of the binder to the diluent is 1:1;
[0545] B3, mixing the above materials to obtain a slurry, wherein the rotation speed of the mixing process is 100 rpm and the mixing time is 1 hour;
[0546] B4, drying the slurry by high-speed centrifugal spraying to obtain the zirconium oxide composite powder, wherein the initial temperature is 290° C., the end temperature is 160° C., the operating frequency of the granulation part of the drying equipment is 4500 rpm, the moisture content is controlled to 1.01%, and the granulation particle size D50 is 109 μm;
[0547] B5, the mass ratio of zirconium oxide to yttrium oxide in the zirconium oxide composite powder obtained in this embodiment is 103:9.0, the zirconium oxide composite powder obtained in Example 1 and the composite powder obtained in this embodiment are mixed in a mass ratio of 4:1, and the mixed zirconium oxide composite powder is pressed at a pressing pressure of 15 MPa to form;
[0548] B6, plastic sealing is performed using a cold isostatic pressure of 170 MPa, and the product is placed in a cold isostatic press for pressurized exhaust;
[0549] B7, bisque firing and debinding at 1105°C;
[0550] B8, engraving;
[0551] B9, finally fired at 1420℃ to form porcelain;
[0552] B10, polishing, glazing and reshaping the blank obtained in step B9 to obtain the dental restoration.
[0553] Comparative Example 17
[0554] This embodiment sequentially prepares the above-mentioned zirconium oxide composite powder and dental restoration according to the following steps:
[0555] B1, providing stabilized zirconia powder, colorant, dispersant, antistatic agent and binder, wherein the mass ratio of the stabilized zirconia powder, colorant, dispersant, antistatic agent and binder is 115:11.0:0.3:0.2:0.8, the colorant is a mixture of neodymium oxide, cobalt oxide and praseodymium oxide in a mass ratio of 11:0.1:1.0, the dispersant is sodium dodecyl sulfate, the antistatic agent is methyl silicone oil, and the binder is phenolic resin;
[0556] B2, diluting the above-mentioned dispersant, antistatic agent and binder with a diluent, wherein the mass ratio of the dispersant to the diluent is 1:2, the mass ratio of the antistatic agent to the diluent is 1:4, and the mass ratio of the binder to the diluent is 1:4;
[0557] B3, mixing the above materials to obtain a slurry, wherein the rotation speed of the mixing process is 20 rpm and the mixing time is 11 h;
[0558] B4, drying the slurry by high-speed centrifugal spraying to obtain the zirconium oxide composite powder, wherein the initial temperature is 250°C, the end temperature is 150°C, the operating frequency of the granulation part of the drying equipment is 4500rpm, the moisture content is controlled to 1.21%, and the granulation particle size D50 is 108μm;
[0559] B5, the mass ratio of zirconium oxide to yttrium oxide in the zirconium oxide composite powder obtained in this embodiment is 106:9.0, the zirconium oxide composite powder obtained in Example 1 and the composite powder obtained in this embodiment are mixed in a mass ratio of 4:1, and the mixed zirconium oxide composite powder is pressed at a pressing pressure of 120 MPa to form;
[0560] B6, plastic sealing is performed using a cold isostatic pressure of 180 MPa, and the product is placed in a cold isostatic press for pressurized exhaust;
[0561] B7, bisque firing and debinding at 1140°C;
[0562] B8, engraving;
[0563] B9, finally fired at 1545℃ to form porcelain;
[0564] B10, polishing, glazing and reshaping the blank obtained in step B9 to obtain the dental restoration.
[0565] Comparative Example 18
[0566] This embodiment sequentially prepares the above-mentioned zirconium oxide composite powder and dental restoration according to the following steps:
[0567] B1, providing stabilized zirconia powder, colorant, dispersant, antistatic agent and binder, wherein the mass ratio of the stabilized zirconia powder, colorant, dispersant, antistatic agent and binder is 119.5:10.0:0.4:0.4:1.0, the colorant is a mixture of neodymium oxide, cobalt oxide and cerium oxide in a mass ratio of 1:1.2:0.1, the dispersant is sodium dodecyl sulfate, the antistatic agent is methyl silicone oil, and the binder is phenolic resin;
[0568] B2, diluting the above-mentioned dispersant, antistatic agent and binder with a diluent, wherein the mass ratio of the dispersant to the diluent is 1:4, the mass ratio of the antistatic agent to the diluent is 1:5, and the mass ratio of the binder to the diluent is 1:1;
[0569] B3, mixing the above materials to obtain a slurry, wherein the rotation speed of the mixing process is 100 rpm and the mixing time is 1 hour;
[0570] B4, drying the slurry by high-speed centrifugal spraying to obtain the zirconium oxide composite powder, wherein the initial temperature is 250°C, the end temperature is 90°C, the operating frequency of the granulation part of the drying equipment is 4500rpm, the moisture content is controlled to 1.15%, and the granulation particle size D50 is 117μm;
[0571] B5, the mass ratio of zirconium oxide to yttrium oxide in the zirconium oxide composite powder obtained in this embodiment is 110:9.5, the zirconium oxide composite powder obtained in Example 1 and the composite powder obtained in this embodiment are mixed in a mass ratio of 4:1, and the mixed zirconium oxide composite powder is pressed at a pressing pressure of 15 MPa to form;
[0572] B6, plastic sealing is performed using a cold isostatic pressure of 250 MPa, and the product is placed in a cold isostatic press for pressurized exhaust;
[0573] B7, bisque firing and debinding at 1200°C;
[0574] B8, engraving;
[0575] B9, finally fired at 1550℃ to form porcelain;
[0576] B10, polishing, glazing and reshaping the blank obtained in step B9 to obtain the dental restoration.
[0577] The zirconium oxide composite powders and dental restorations obtained in the above-mentioned embodiments and comparative examples were subjected to performance tests, and the obtained test data are listed in the following Tables 1 to 6.
[0578] The specific operation methods of each performance test are as follows:
[0579] Powder evaluation method:
[0580] ① Fluidity: standard funnel method (Hall flowmeter), weigh 50g±0.1g powder sample, block the small hole of the funnel, pour the powder sample into the funnel, open the small hole, use a stopwatch (accuracy 0.2s) to time until the powder sample flows out, stop the timing, record the falling time of 50g powder, test three times in a row and take the arithmetic average, which is the fluidity of the material (GB / T 1482-2022).
[0581] ② Loose density: Funnel method. Before testing, level the instrument first, rotate the horizontal adjustment foot to adjust the bubble of the level indicator of the loose density tester to the center point; use the iron cone rod provided by the instrument to block the feed port of the tester, then pour the powder into the funnel, pull out the iron cone rod, and the powder will flow out freely and fall into the receiving container. After the fall is completed, use an iron ruler to scrape the surface of the receiving container to remove the excess material; record the mass and volume of the outflowing powder (the fixed volume of the container is 100cm 3) and calculate the bulk density (GB / T 1479.1-2011).
[0582] The calculation formula for bulk density is: weight (g) ÷ 100 = bulk density, the unit is g / cm3.
[0583] ③ Sphericity ratio: Shake the powder evenly before testing and pour it on the double-sided tape. Use an ear bulb to blow off the unattached powder to spread the powder particles evenly. Adjust the microscope to a fixed magnification and record the total number of powder particles in the microscope field of view as A. Compare it with the standard critical sphere. The total number of "apple-shaped balls", "shrunken balls" and "agglomerates of multiple balls" with worse sphericity than the critical sphere is recorded as B.
[0584] The sphericity ratio calculation formula is: (AB) / A*100%.
[0585] ④ Hollowness ratio: According to the sample preparation method of sphericity ratio, after the powder is spread on the double-sided tape, a new double-sided tape is used to stick to the double-sided tape with the powder, and then gently pressed and torn off (the purpose is to peel off the particles and reveal the cross-section of the particle sphere); adjust the microscope to a fixed magnification, record the total number of particles in the powder cross-section within the microscope field of view as A, and according to the hollow ball judgment standard: the hollow area> 1 / 2 of the sphere is judged as a hollow ball, and the total number is recorded as B.
[0586] The calculation formula for hollowness ratio: B / A*100%.
[0587] Powder evaluation method:
[0588] ① Strength: After mixing, the colored powder is pressed into a square with a side length of 30mm and a thickness of 12mm in a specific mold. The square is treated with low-temperature debinding. The pre-burned sample after debinding is cut longitudinally into a 1.5±0.2mm thick spline. The spline is sintered at high temperature to form porcelain. After forming porcelain, the spline needs to be polished. The strength test instrument is a universal mechanical testing machine, and it is used in conjunction with the supporting analysis software; before the test, the width and thickness of the upper, middle and lower parts of the spline are measured and input into the test software, and the spline is placed on a specific fixture of the mechanical testing machine, and pressure is applied. The test automatically records the stress when the spline breaks and automatically calculates the three-point bending strength of the spline based on the input spline size. The average value of 10 splines is taken for each sample.
[0589] ② Transparency (background contrast method): After mixing, the colored powder is pressed into a square with a side length of 30mm and a thickness of 20mm in a specific mold. The square is treated with low-temperature debinding. The pre-burned sample after debinding is cut into a sample with a thickness of 1.30±0.1mm. The sample is sintered at high temperature for a second time to become porcelain. After becoming porcelain, the sample strip needs to be polished and ground to ensure that the thickness is 1.00±0.01mm before testing. The reflectivity meter is used for the transparency test. The sample is placed in the center of the light transmission hole, the black shading plate is placed on the sample, the shading cover is covered, and the value at this time is recorded; the white shading plate is placed on the sample, the shading cover is covered, and the value is recorded. The black value is divided by the white value to obtain the reflectivity value.
[0590] ③ Color difference: After mixing, the colored powder is pressed into a small disc with a diameter of 10mm and a thickness of 3mm in a specific mold. The small disc undergoes low-temperature debinding and high-temperature secondary sintering to become porcelain. The Lab value of the porcelainized disc is tested on a professional colorimeter and compared with the Lab value of the standard sample. The color difference (△E) is calculated using the formula.
[0591] Randomly select 5 groups of samples from the same batch to test △E, and the extreme value is the color difference uniformity within the batch.
[0592] Color difference (△E) calculation formula: [(△L) 2 +(△a) 2 +(△b) 2 ]^(1 / 2).
[0593] ④ The mass ratio of zirconium oxide to yttrium oxide in the zirconium oxide composite powders obtained in all the embodiments and comparative examples recorded in the specification of the present invention is measured by XRF; it is worth mentioning that X-ray fluorescence spectrometer (XRF spectrometer for short) is a rapid, non-destructive material measurement method. X-ray fluorescence (XRF) is the secondary X-ray excited when a material is bombarded with high-energy X-rays or gamma rays, and can be used to determine the composition of ceramic powders.
[0594] Table 1 Performance parameters of the composite powders and dental restorations obtained in Examples 1 to 6
[0595]
[0596]
[0597] Table 2 Performance parameters of the composite powders and dental restorations obtained in Examples 7 to 12
[0598]
[0599]
[0600]
[0601] Table 3 Performance parameters of the composite powders and dental restorations obtained in Examples 13 to 18
[0602]
[0603]
[0604] It can be seen from Tables 1 to 3 above that the powder flowability of Examples 1-18 meets 40 to 120 seconds.
[0605] From Table 1 above, it can be seen that the dilution ratio of the dispersant in Examples 2 and 3 is optimal at 1:(5-10), and the dispersion effect is the best; after the dispersant is diluted, the -COO - The long molecular chain structure of the functional group, in which -COO - It is adsorbed on the surface of the primary particles after grinding. As the dosage increases, the Zeta potential of the particles in the slurry changes from positive to negative. In this process, the soft agglomerates produced by grinding are deagglomerated by the charge repulsion, and due to the steric hindrance effect of the long molecular chain of the dispersant, the primary particles no longer clump together, which is beneficial to the subsequent granulation and processing into porcelain and reduces internal defects.
[0606] As can be seen from Table 2 above, for Examples 7, 8, and 9, within a certain range, as the amount of antistatic agent added increases, the fluidity improves, the strength extreme difference decreases, and the color difference decreases. Antistatic agents are mostly alcohols and ethers, and contain hydrophilic groups and lipophilic groups. During the drying process, the hydrophilic group will absorb moisture from the air and form a thin conductive layer on the surface of the particles, and the static charge can be conducted through this conductive layer. During the drying process, friction between particles and friction between granulation particles and the inner wall of the equipment affect the smoothness of the surface of the granulation balls, and thus affect the fluidity of the powder.
[0607] It can be seen from Table 1 and Table 3 above that for Examples 1 to 4 and Examples 13 to 16, the frequency of the granulating component is controlled to control the rotational speed. The higher the rotational speed, the more complete the drying, the lower the moisture content of the powder, the higher the probability of static electricity generated during the drying process, the worse the surface smoothness of the granulating balls, the worse the fluidity, and the obvious effect on the powder strength.
[0608] As can be seen from Table 1 and Table 2 above, by comparing Examples 1 to 3 with Examples 8 to 10, and by comparing Examples 5 to 6 with Examples 14 to 15, it can be seen that the fluidity of the rotary flash evaporator, the paddle dryer, and the granulated powder is poorer than that of the high-speed centrifugal spray. The reason is that the centrifugal spray is thrown out by the atomizing disk during the drying process to form droplets, which are more easily spherical under the action of surface tension; the sphericity ratio is higher.
[0609] From Table 1 to Table 3 above, it can be seen that Examples 1 to 9 and Examples 10 to 18 all show a trend of gradually increasing yttrium content. Within a certain range, the higher the yttrium content, the lower the strength value; the reason is that yttrium is used as a stabilizer, and its cation Y 3+ Can replace Zr in zirconia 4+ , forming a substitutional solid solution, thereby hindering the transformation of tetragonal to monoclinic crystals, and stably lowering the phase transition point of zirconia to room temperature, but too much yttrium will hinder the crystallization of zirconia during the sintering process, causing the relative density to gradually decrease, thereby affecting the fracture strength of the material; at the same time, when the fluidity is between 60 and 90 seconds, the strength range is optimal; at this time, the different colors of powders are mixed most evenly during the mixing process, and the color difference range is minimal.
[0610] Table 4 Performance parameters of the composite powders and dental restorations obtained in Comparative Examples 1 to 6
[0611]
[0612]
[0613] Table 5 Performance parameters of the composite powders and dental restorations obtained in Comparative Examples 7 to 12
[0614]
[0615]
[0616] Table 6 Performance parameters of the composite powders and dental restorations obtained in Comparative Examples 13 to 18
[0617]
[0618]
[0619] From the above table, we can see that if the diluent ratio is too low, it will affect the dispersion performance of dispersants, antistatic agents, binders and other molding aids in the slurry. In the initial stage of addition, if the additives are locally excessive and the concentration is too high, it will affect the hollowness and surface smoothness of the granulated balls, and thus affect the fluidity of the powder.
[0620] As can be seen from Table 4 above, for Comparative Examples 1 to 6, if the frequency of the granulation components is too high or too low, the rotation speed is too high, which will lead to too small granulation balls. The too small granulation balls will adhere to the surface of the large granulation balls, affecting the fluidity of the powder; in addition, the particle size of the small granulation balls is relatively hard, and it is not easy to crush them under the same conditions as the normal granulation balls, which not only affects the extreme matching effect, but also causes local defects and affects the strength; the rotation speed is too low, the powder moisture is high, it is not fully dried, and the granulation balls adhere to each other, which also affects the strength, and the mixing with the color powder is uneven, which significantly affects the batch color consistency, that is, the color difference is extremely obvious. As can be seen from Table 3 above, for Example 18, the temperature of the granulation equipment is too high. Because the auxiliary agent is an organic compound, after being baked at too high a temperature, the bonding effect is reduced, resulting in the powder being unable to be pressed and formed in the subsequent processing process, and the porcelain-forming performance cannot be evaluated.
[0621] It can be seen from Table 6 above that for Comparative Examples 13 to 15, polyurethane is used as a binder. During the stirring process in the slurry, the polyurethane itself will undergo a polymerization reaction, and the slurry will be stratified, which will affect the bonding effect with the original particles. The powder bonding effect is poor, the strength is low, and the color consistency is good (the color difference extreme difference △E <0.5).
[0622] As can be seen from Table 4 and Table 5 above, for Comparative Examples 3-4, 9-18: sodium dodecylbenzene sulfonate, sodium dodecyl sulfate, and sodium dodecyl sulfonate are used as dispersants. After dilution and addition, the slurry foams severely under high-speed stirring conditions. Due to the foaming of the slurry, the high-speed centrifugal spray equipment has unstable feeding of the feed pump, or does not feed, the equipment outlet temperature is unstable, the spray equipment hangs on the wall seriously, the powder morphology deteriorates, and the performance of the finished product deteriorates significantly. The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can easily think of changes or replacements within the technical scope disclosed by the present invention, which should be covered within the protection scope of the present invention. Therefore, the protection scope of the present invention shall be based on the protection scope of the claims. In addition, the specification uses specific examples to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core ideas. The content of this specification should not be understood as a limitation on the present invention.
Claims
1. A zirconium oxide composite powder, characterized in that: The zirconium oxide composite powder comprises: stabilized zirconium oxide powder and additives; Wherein, the auxiliary agent includes: The dispersant is preferably at least one of propylene glycol methyl ether, sodium polymethacrylate, polyacrylamide, sodium oleate, polyethylene ether, sodium hexametaphosphate, and sodium tripolyphosphate; The antistatic agent is preferably at least one of glycerol fatty acid ester, lauryl alcohol, dodecanol, n-octanol, glycerol, polyethylene glycol, diethylene glycol methyl ether, and octadecylamine polyoxyethylene ether; The binder is preferably at least one of ammonium polyacrylate, polyvinyl alcohol, polymethyl methacrylate, carboxymethyl cellulose, sodium alginate, and polyethylene oxide; The mass ratio of the stabilized zirconia powder, dispersant, antistatic agent and binder is (87-115):(0.5-5):(0.5-10):(1.0-10), preferably (90-105):(1-3):(1-3):(1-3); the mass ratio of zirconium oxide and yttrium oxide in the stabilized zirconia powder is (85-100):(2-15), preferably (85-95):(5-10).
2. The zirconium oxide composite powder according to claim 1, characterized in that: The zirconium oxide composite powder also includes a colorant. In the zirconium oxide composite powder, the mass ratio of the stabilized zirconium oxide powder, colorant, dispersant, antistatic agent and binder is (87-115):(0.01-10):(0.5-5):(0.5-10):(1.0-10), preferably (90-105):(0.01-5):(1-3):(1-3):(1-3).
3. The zirconium oxide composite powder according to claim 1, characterized in that: The zirconium oxide composite powder has at least one of the following characteristics: loose Packing density is 1~1.6g / cm 3 , The powder fluidity is 40 to 120 seconds. The particle size D50 is 40 to 80 μm.
4. The zirconium oxide composite powder according to claim 2, characterized in that: The colorant is at least one of chlorides, oxides or nitrates of iron, manganese, neodymium, cobalt, praseodymium or cerium; The particle size D50 of the oxides of iron, manganese, neodymium, cobalt, praseodymium and cerium is 0 to 10 μm.
5. The zirconium oxide composite powder according to any one of claims 1 to 4, characterized in that The zirconium oxide composite powder has at least one of the following characteristics: The sphericity ratio of the zirconium oxide composite powder is greater than 95%; The hollowness ratio of the zirconium oxide composite powder is less than 10%; The color difference ΔE of the zirconium oxide composite powder is less than 0.
5.
6. A method for preparing the zirconium oxide composite powder according to any one of claims 1 to 5, characterized in that: The method comprises the following steps: S1, providing stabilized zirconium oxide powder and additives; S2, diluting the dispersant, antistatic agent and binder in the auxiliary agent with a diluent; S3, mixing the stabilized zirconia powder, the diluted dispersant, antistatic agent, binder and water to obtain a slurry; S4, drying the slurry to obtain the zirconium oxide composite powder.
7. The method according to claim 6, characterized in that The stabilized zirconium oxide powder is obtained by the following method: A1, mixing zirconium nitrate and water to obtain a zirconium nitrate aqueous solution; A2, adding a stabilizer to the zirconium nitrate aqueous solution obtained in step A1, and performing a synthesis reaction; A3, filter-pressing and calcining the solution obtained in step A2 to obtain the stabilized zirconium oxide powder.
8. The method according to claim 7, characterized in that Include at least one of the following characteristics: In the step A1, the mass ratio of the zirconium nitrate to water is 1:(1-10); In the step A2, the zirconium nitrate and the stabilizer are kept at 100 to 170° C. and reacted for 5 to 70 hours; In the step A3, the solution obtained in the step A2 is filtered under a pressure of 0.1 to 5 MPa, the calcination temperature is 800 to 1300° C., and the insulation time is 2 to 10 hours.
9. The method according to claim 7, characterized in that: The diluent is at least one of alcohols, ketones, ethers, esters and water.
10. The method according to claim 7, characterized in that Have at least one of the following characteristics: In the step S2, the mass ratio of the dispersant to the diluent is 1:(5-15); In the step S2, the mass ratio of the antistatic agent to the diluent is 1:(5-15); In the step S2, the mass ratio of the binder to the diluent is 1:(5-15).
11. The method according to claim 7, characterized in that In the step S3, the mass ratio of the stabilized zirconium oxide, the diluted dispersant, the diluted antistatic agent, the diluted binder, and water is (87-115):(5-50):(5-100):(1-100):(200-250); And / or, in step S3, the mixing rate is 30-90 rpm and the mixing time is 2-10 h.
12. The method according to claim 7, characterized in that The step S1 also provides a colorant; S3, mixing the stabilized zirconia powder, the colorant, the diluted dispersant, the antistatic agent, the binder and water to obtain a slurry; The mass ratio of the stabilized zirconium oxide, the colorant, the diluted dispersant, the diluted antistatic agent, the diluted binder and water is (87-115):(0.01-10):(5-50):(5-100):(1-100):(200-250).
13. The method according to claim 6, characterized in that In step S4, the drying method is one of rotary flash evaporation, high-speed centrifugal spraying, blade drying, and boiling drying, or a combination of at least two of them.
14. The method according to claim 6 or 13, characterized in that: In step S4, the slurry is dried by high-speed centrifugal spraying, wherein: The initial temperature is 180-280°C, preferably 200-250°C; The end temperature is 100-150°C, preferably 100-120°C; The operating frequency of the granulating part of the drying equipment is 5000-15000rpm, preferably 8000-12000rpm, and the moisture content is controlled to be 0-1.0%, preferably 0.2-0.8%; The particle size D50 of the zirconium oxide composite powder produced by granulation is 20 to 100 μm, preferably 40 to 80 μm.
15. A dental restoration, characterized in that: The dental restoration is made of the zirconium oxide composite powder according to any one of claims 1 to 5, or is made of the zirconium oxide composite powder obtained by the method according to any one of claims 6 to 14.
16. A method for preparing a dental restoration according to claim 15, characterized in that The method comprises the following steps: A10, powder dry pressing: placing the zirconium oxide composite powder into a dry pressing machine mold for pressing; A20, cold isostatic pressing: the compressed zirconium oxide composite powder obtained in step A10 is sealed in plastic and placed in a cold isostatic press to pressurize and exhaust; A30, bisque firing and debinding: heating the zirconia composite powder obtained in step A20 and being cooled and isostatically pressed; A40, final firing of porcelain: firing the bisque-fired zirconium oxide composite powder obtained in step A30 to obtain a bisque; A50, post-processing: polishing, glazing and reshaping the blank obtained in step A40 to obtain the dental restoration.
17. The method according to claim 16, characterized in that Have at least one of the following characteristics: In the step A10, at least two of the zirconium oxide composite powders are mixed and then placed in the dry pressing mold for pressing, wherein at least one of the zirconium oxide composite powders does not contain a colorant, and at least one of the zirconium oxide composite powders contains a colorant; In the step A10, the pressing pressure is 15-25 MPa; In the step A20, the cold isostatic pressure is 180-250 MPa; In the step A30, the heating temperature is 1000-1100° C.; In the step A40, the firing temperature is 1400-1500°C.
18. The method according to claim 16, characterized in that There is also a step A35 between step A30 and step A40, wherein step A35 is engraving: engraving the bisque-fired zirconium oxide composite powder obtained in step A30; Furthermore, in the step A40, the engraved zirconium oxide composite powder obtained in the step A35 is fired to obtain the green blank.